Les sources - Drine, Ali (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie – Djerba

Salah Shibub al Jerbi: itinéraire sinueux d'un mkhazni dans la Régence de Tunis au XIXe siècle - Ben Tahar, Jamel (Individu et pouvoir dans les pays islamo-méditerranéens, 2009)
Keywords: Biographies – Djerba – 19e siècle

المرأة في شعر الخوارج - صالح, إبراهيم حسن (مجلة جامعة تكريت للعلوم الإنسانية, 2009)
أساليب التوكيد في شعر الخوارج
Keywords: Poésie kharijite

السرد في كتاب "الكامل في اللغة والأدب" أخبار الخوارج مثالاً - عبيد, عباس (مجلة آداب المستنصرية, 2009)
إن الأخبار الواردة في مثل الغرباء تشترك جميعها في مغزى أن قضبان القياس في التفكير في أسس المنطق الفريد لسيطرة رؤية واحدة ومصادرة الرأي الآخر ، إبن السيد أبو علي الفارسي ، سموا بالهره لأن هم الهواء والغضب…
Keywords: Kharijisme

التفسير المنحرف والباطني عند الخوارج - محمد, شهاب احمد (مجلة كلية التربية الأساسية, 2009)
لحمد الله رب العالمين ، والصلاة والسلام على سيد المرسلين ، سيدنا محمد وعلى أله وصحبه أجمعين : وبعد فأن التفسير عند الفرق الإسلاميّة يحظى باهتمام الباحثين والدارسين لا سيما إذا كانت هذه الفرقة المراد التعريف…
Keywords: Kharijisme

التحول الديمقراطي في سلطنة عمان: الواقع والتحديات وآفاق المستقبل - بني سلامة, محمد تركي (مجلة دراسات الخليج والجزيرة العربية, 2009)
تهدف هذه الدراسة إلى إلقاء الضوء على واقع التجربة الديمقراطية في سلطنة عُمان، عبر تعريف المفاهيم الأساسية في الدراسة، وتطورها التاريخي، ولا سيما بعد انطلاق الموجة الثالثة للتحول الديمقراطي في العالم، ثُم تتناول مفهوم الديمقراطية، وأنواعها، والمتطلبات التي لا بد من توافرها في نظام سياسي حتى يمكن اعتباره ديمقراطياً. ثم تتناول التحول الديمقراطي في سلطنة عُمان، الذي هو في حقيقته ناتج من رغبة صانع القرار في تبني الخيار الديمقراطي أسلوباً في الحكم أكثر منه تكتيكاً لمواجهة بعض المشكلات، ولا سيما الاقتصادية، بعد تراجع إنتاج النفط والغاز. وقد تناولت الدراسة عمق الإصلاحات السياسية التي تم اتخاذها، وخصائص التجربة العمانية، حيث أكدت دور المؤسسات السياسية - وفي مقدمتها الأحزاب السياسية، والثقافة الديمقراطية - في تسريع عملية التحول الديمقراطي، وعرضت لأبرز المعوقات والتحديات السياسية والاقتصادية التي تبطئ عملية التحول الديمقراطي. وأخيراً، تم استشراف مستقبل التجربة الديمقراطية في سلطنة عُمان، في ضوء الضغوط المحلية والدولية والإقليمية، وقد خلصت الدراسة إلى أن التجربة الديمقراطية في سلطنة عُمان هي تجربة رائدة، وقابلة لمزيد من التطور والتقدم.

المنهج الدعوي للنظم الاجتماعية لإباضية وادي ميزاب - أولاد عمارة, صالح بن عبد الحميد (كلية العلوم الشرعية, 2009)

دبوان: نفحات ولفحات - دواق, سليمان بن عمر (جمعية التراث, 2009)
Keywords: Poésie – Mzab

الخافق الصادق: شعر - ناصر, محمد صالح (دار الريام للنشر والتوزيع, 2009)
Keywords: Poésie – Mzab

أمجادنا تتكلم وقصائد أخرى - زكرياء, مفدي (موفم للنشر،, 2009)
يتناول كتاب (أمجادنا تتكلم وقصائد أخرى) والذي قام بتأليفه (مفدي زكرياء) في حوالي (298) صفحة من القطع المتوسط موضوع (فخامة الرئيس عبد العزيز بو تفليقة) مستعرضا المحتويات التالية : تصدير فخامة رئيس الجمهورية السيد عبد العزيز بو تفليقة، مفدي زكاريا في سطور، أمجادنا تتكلم وقصائد أخرى، تهنئة بمولود، مدح وفخر، موشحة زكريا بن سليمان، إلى الريفيين، عيد سعيد، تحية الشبيبة الميزانية لسفارة الشيخ سليمان باشا الباروني

الوقف التعليمى في عمان وأثره على الحركة العلمية - الكندي, أحمد بن يحيى بن أحمد (الندوة الدولية: الوقف في عمان بين الماضي والحاضر, 2009)
Accepted: 2023-04-12T18:48:51Z Publisher: جامعة آل البيت

Abū Zakariyyā al-Janāwunī - Pakatchi, Ahmad (Encyclopaedia Islamica Online, 2009)
Keywords: Biographies – Djebel Nefousa; Jannāwunī; Yaḥyā b. al-Khayr

Islam in oman - Bos, Michael (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)

Oman and Sinbad in the tales of the thousand and one nights - Howes Smith, Fleur (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Littérature – Oman

Frankincense and more. Oman's fragrant heritage - Mershen, Birgit (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)

A blend of local traditions and foreign influences. Art and architecture in oman - Mols, Luitgard (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Architecture – Oman

Art in silver. Traditional jewellery from oman - Mols, Luitgard (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Artisanat – Oman

From khanjars to tweezer-cases. Omani weapons and accessories for men - Mols, Luitgard (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)

Oman: catalogue created for the Oman exhibition in De Nieuwe Kerk, Amsterdam, from 17 October 2009 to 18 April 2010 - Mols, Luitgard; Boelens, Birgit (De Nieuwe Kerk, 2009)
Keywords: Arts – Oman

Rulers of Oman from the last two dynasties - Mols, Luitgard; Boelens, Birgit (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)

Oman in history - Rasbi, Khalifa Khamis al- (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)

Archaeology in oman. Local and international trade - Sabri, Biubwa Ali al- (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Archéologie – Oman

Historical Ties Between Oman and the European Powers - Slot, Ben (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Politique étrangère – Oman

Traditional architecture of forts and mosques in oman - Tamimi, Ahmed Mohammad al- (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Architecture – Oman

Omani dress - Vogelsang-Eastwood, Gillian (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Artisanat – Oman

Arabian ships. The dhow - Vosmer, Tom (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Navigation – Oman

دور الميزالبيين في الثورة التحريرية بمدينة العلمة - لمسن, الناصر بن بابا (جمعية التراث, 2009)
Keywords: Urbanisme – Mzab

Historique de l'épopée du chant Qassamen: depuis sa laborieuse naissance comme chant de la Révolution algérienne jusqu'à son officialisation en tant qu'hymne national de la République algérienne - Bechichi, Lamine; Benhamida, Abderrahmane (Éditions Alpha, 2009)
Keywords: Hymne national – Algérie

فن الرثاء عند شاعرات الجاهلية - الصباري, خميس بن ماجد بن خميس (جامعة نزوى, 2009)
Keywords: Poésie

La mémoire (bafouée) d'une mosquée - Bouabid, Naceur (Le Temps, 2009)
Keywords: Architecture – Djerba; Bûlaymân; Mosquée (Ja’bîra; Djerba); Monuments – Djerba

الإمام جابر بن زيد - الجعبيري, فرحات‏ بن علي (JMS Plus, 2009)
Keywords: Biographies – Oman

بعض المنشآت المائية بجبل دمر: تقنيات الإنشاء ومشاكل الاستغلال - الثابتي, علي (الماء والتعمير ببلاد المغرب في العهدين القديم والوسيط: أعمال الندوة الدولية الثالثة المنعقدة بالمكتبة الوطنية بتونس أيام 15-16-17 نوفمبر 2007 = eau et peuplement au Maghreb durant l'Antiquité et le Moyen âge, 2009)

الماء والتعمير ببلاد المغرب في العهدين القديم والوسيط: أعمال الندوة الدولية الثالثة المنعقدة بالمكتبة الوطنية بتونس أيام 15-16-17 نوفمبر 2007 = eau et peuplement au Maghreb durant l'Antiquité et le Moyen âge - حسن, محمد (كلية العلوم الإنسانية والاجتماعية, 2009)

أين ذهبت المصادر النكرية؟ - بن يحياتن, ساسي بن عمر (Al-Jazira | الجزيرة, 2009)
Keywords: Jaddi Isa; mosquée (Robbana; Djerba); Monuments – Djerba

الإمام إسماعيل الجيطالي وفكره العقدي المتوفى سنة 750 هـ، 1349 م - باباواعمر, خضير بن بكير (جمعية التراث, 2009)

معهد الحياة : نشأته وتطوره - شريفي, سعيد بن بالحاج (جمعية الحياة, 2009)
Keywords: Enseignement – Mzab

فتح المقتدر في أحكام الحاج و الزائر والمعتمر - الكندي, عبد الله بن سيف (المؤلف, 2009)

رفع الإشكال عن بعض المسائل المتعلقة برؤية الهلال - القنوبي, سعيد بن مبروك (وزارة الأوقاف والشؤون الدينية, 2009)

من لا يعرف الإباضية. المعرفة والتعارف والإعتراف - بافولولو, صالح بن داود (مطبعة الواحات, 2009)

شخصية من الشخصيات الغرداوية التاريخية، الدينية، التربوية، الاجتماعية، الأدبية، التي استوقفتاني: الشيخ حمو بن عمر بن إسماعيل فخار 1917-2005 - نجار, مصطفى عمر (2009)

الكرامة : دراسة عقدية - الخلايلة, أحمد عبدالحفيظ فلاح (جامعة آل البيت, 2009)
University: كلية الدراسات الفقهية والقانونية

الجاليات العربية الإسلامية المبكرة في غرب أفريقيا وأثرها في نشر الإسلام واللغة العربية - الدهماني, الدهماني سالم (المجلة العلمية بكلية الآداب, 2009)
Keywords: Invasion arabe – Afrique du Nord

مناقشات الجلسة السابعة - الزحيلي, وهبة بن مصطفى; العبري, علي بن هلال; العلوي, سعيد; مدكور, عبدالحميد عبدالمنعم; إمام, محمد كمال الدين (اعمال ندوة تطور العلوم الفقهية: فقه التوقع: ‏المنعقدة خلال عام 1430هـ/2009م, 2009)

أحمد بن سليمان بن النظر السمائلي : عصره - سيرته - ما وصل إلينا من آثاره - السليمي, محمود بن مبارك بن حبيب (مجلة دراسات تاريخية, 2009)

موقف فقهاء القيروان من السلطة الأغلبية - الهيلة, محمد الحبيب (إشعاع القيروان عبر العصور : وقائع الندوة التي إنعقدت بالقيروان من 20 إلى 25 أفريل 2009 / المجمع التونسي للعلوم والآداب والفنون, 2009)

البعد الحضاري لتفسير القرآن عند الإباضية - الوائلي, سعيد بن سليمان (جامعة الزيتونة, 2009)
Keywords: Coran – Commentaires

الأباضية في ضوء الكتاب والسنة - سليمان, أسامة بن علي (التوحيد, 2009)
Number: 448

الإصرار على الذنب وأثره فى العمل عند الإباضية - وينتن, مصطفى بن الناصر (مجلة جامعة الأمير عبد القادر للعلوم الإسلامية, 2009)

الصحيفة القحطانية - ابن رزيق, حميد بن محمد بن بخيت (وزارة التراث والثقافة, 2009)
Keywords: Sources – Oman

إرشاد الطالب إلى فقه الإسلام (أركان الإسلام الخمسة) في الأيمان والصلاة والزكاة والصوم والحج بأسلوب قريب، ولغة سهلة - الطيواني, خلفان بن سليمان (2009)
Keywords: Fiqh; Fiqh – Traité

التحليل المكاني لاستعمالات الأراضي السكنية لمدينة الزاوية - الرقيبي, محمد أبوغرارة عريبي (جامعة طرابلس, 2009)
\
Keywords: Urbanisme – Zouara

البحث في المقاربات التأريخية للموسيقى العربية و التونسية مذكرة بحث لنيل شهادة الماجستير في الموسيقى و العلوم الموسيقية - الطرابلسي, فراس (المعهد العالى للموسيقى, 2009)

الهجرة الهلالية و أثرها في تغيير البنية الاجتماعية لبلاد الزاب - عمارة, علاوة (مجلة الآداب و العلوم الإنسانية, 2009)
لقد قدمت الدراسات الكلاسيكية عدة تفسيرات لتاريخ المغرب الوسيط ربطته في أغلبها بدور الكيانات السياسية التى تأسست في مناطق الشمال في تحديد مصاره . غير أن الاهتمام سرعان ما انتقل إلى مناطقه الجنوبية المشتهرة بثقافته الواحية في محاولة لدراسة تاريخ العنصر الإباضي المستقر أساسا بمدن ميزاب و بجبل نفوسة .

الإباضية والمعتزلة في عهد الدولة الرستمية - أبو عمران, الشيخ (الدراسات الإسلامية, 2009)
بدون ملخص

دراسة وثيقة تاريخية للإمام أفلح بن عبد الوهاب الرستمي بعنوان: " النصيحة العامة من الإمام أفلح بن عبد الوهاب إلى كل من كان تحت لوائه من المسلمين" - بوركبة, محمد (المجلة الجزائرية للمخطوطات, 2009)
مؤلف هذه الوثيقة، هو أفلح بن عبد الوهاب بن عبد الرحمن بن رستم، ثالث أئمة الدولة الرستمية الإباضية، بويع بالإمامة بعد وفاة والده عبد الوهاب (198-247ﻫ/814-861م)، واتبع نهج أبيه عبد الوهاب بن عبد الرحمن في تسيير شؤون الدولة الرستمية، وعدل بين الرعية بالحق. وكان تقيـا وورعا، مما دفع الإباضيين في المجتمع الرستمي إلى التمسك به إماما وحاكما عليهم. عنى الإمام أفلح بن عبد الوهاب بنشر الأمن والسلم في ربوع الدولة فتطورت الحضارة الإباضية الرستمية في عهده ووصلت إلى ذروتها من العز والتقدم، حيث بنى الأغنياء القصور الفخمة واتخذت الضياع الواسعة، وكثر العبيد والحشم، واتسع نطاق التجارة اتساعا واسعـا من المشرق الإسلامـي إلى السودان.
Keywords: Dynastie rustumide

التأريخ والموسوعية عند علماء الإباضية -الوارجلاني والمُصعبي والقُطب أطفيَّش أنموذجا- - حاج أمحمد, يحيى بن بهون (مجلة الواحات للبحوث والدراسات, 2009)
التأريخ والموسوعية عند علماء الإباضية -الوارجلاني والمُصعبي والقُطب أطفيَّش أنموذجا-

Orientalism and relationships between Islam and The West - Salimi, Abdulrahman al- (Krakowskie Studia Międzynarodowe, 2009)
"Since the end of the Second World War, a dispute has continued amongst Muslims and Arabs regarding the character of Orientalism. The period during the Cold War played a principal role in the shaping of disparate views when some of the key Arab states leaned towards the former Soviet Union, while others aligned themselves with the United States and its allies. Such alignments resulted in distinctive orientations towards cultural studies that found expression in a ‘soft’ confrontation led by Islamists on one side and leftwing leaders on the other. In exploring these differences, it is important to begin by defining what is meant by Orientalism. To do this, one needs to examine the three main areas of scholarly focus in the last two hundred years: the editing of Arabic manuscripts, historical scholarship on Islam, and Islamic religious studies and its associated branches."(...)

A fatal duel: 'Harry Alis' (1857-95), a behind the scenes figure of the early Third Republic - Wilkinson, John Craven (Antony Rowe, 2009)
Don de l'auteur

Les Actes de la Conférence de Carthage (411): un document trop ignoré du Bas-Empire - Lamirande, Emilien (Les Pères et la naissance de l'ecclésiologie, 2009)
Keywords: Donatisme

تجربة وقف الكتب - مصلح, أحمد بن مهني (الندوة الدولية: الوقف في عمان بين الماضي والحاضر, 2009)
Keywords: Waqf (fondations) – Djerba

Sufriyye الصفريّة İlk Hâricî fırkalarından biri - Dalkiliç, Mehmet (İslâm Ansiklopedisi, 2009)
Keywords: Sufrisme

تطور عمران مدينة وارجلان خلال العصر الإسلامي القصر العتيق نموذجا دراسة تاريخية أثرية - عاشور, صيد (جامعة محمد خيضر, 2009)

مستويات التشكيل الإبداعي في شعر صالح خرفي - دكدوك, بلقاسم (جامعة الحاج لخضر, 2009)
Keywords: Poésie – Mzab

قاعدة النظر إلى المآل وأثرها في الفقه الإسلامي دراسة مقارنة في العقود و التصرفات - بابكر, خالد بن محمد (جامعة الأمير عبد القادر, 2009)
Keywords: Fiqh

معالم النهضة الإصلاحية عند إباضية الجزائر من سنة 1157هـ/1744م - الى سنة 1382هـ/1962م - الشيخ بالحاج, قاسم بن أحمد (جامعة الجزائر, 2009)
Keywords: Réformisme – Mzab

المؤسسات العرفية بمنطقتي القبائل ووادي مزاب ومساهمتها في المرافق العامة مقاربة أنتروبولوجية قانونية - نوح, عبد الله (جامعة الجزائر, 2009)
Keywords: Droit coutumier – Mzab

تقويم الكفايات التدريسية لأستاذ التعليم الثانوي دراسة ميدانية بولايتي ورقلة وغرداية - بوسعدة, قاسم (جامعة الجزائر, 2009)
Keywords: Enseignement – Mzab

الدور البريطاني في النزاع بين السلطنة والإمامة في عمان 1913-1965 - العمري, ثابت غازي بدر (جامعة اليرموك, 2009)
Keywords: Vie politique – Oman – 1932-1970

المسايرة والمغايرة الاجتماعية في الوسط المدرسي الجزائري دراسة فروق بين تلاميذ ثانويات مجتمعي بني مزاب والجلفة - بكاي, ميلود (جامعة بن يوسف بن خدة, 2009)

المخيال وإعادة إنتاج الرموز الاجتماعية دراسة في البنية الرمزية للمجتمع المحلي الميزابي بين الأصول الأولى والتحولات الراهنة: مقاربة سوسيو- أنتروبولوجية لحالة قصر غرداية - عبد النور, محمد (جامعة الجزائر, 2009)

المسجد العتيق لبلدة بني يزقن (مزاب) - الحاج سعيد, يوسف بن بكير (المطبعة العربية, 2009)
Keywords: Architecture – Mzab

Les accords de cessation des hostilités dans le processus de paix, en république du Congo Brazzaville - Okiemba, Rock (Université Paris 8, 2009)

L'Union pour la Méditerranée, est-elle une opportunité pour les pays du Maghreb ? Cas de l'Algérie - Meziane, Karima (Université Paris 8, 2009)

Le rôle des filles aînées au sein de la famille algérienne - Nechab, Djamila (Université Paris 8, 2009)

أخبار وأيام وادي ريغ للشيخ:محمد الطاهر بن دومة (1336 -1403هـ/1918-1982م) - بن عون, محمد الحاكم (جامعة منتوري, 2009)

«أهلُ الله وخاصَّتُه»؛ المستظهرون لكتاب الله العزيز بالقرارة (الحياة, 2009)

أهمية توثيق عقد الزواج، ومخاطر الزواج العرفي على الأسرة والمجتمع - أبو بكر, صالح بن عبد الله (الحياة, 2009)
Keywords: Droit coutumier – Mzab

الأطعمة الـمُصنَّعة الحديثة، بين التأصيل الشرعي والتحليل العلمي - أرفيس, أحمد بن محمد (الحياة, 2009)

تحية لوادي ميزاب - السيابي, عبد الله بن راشد (الحياة, 2009)

مدلول كلمة "حرب" في القرآن الكريم - الشيخ بالحاج, عيسى بن محمد (الحياة, 2009)

قراءة في رسالة مهرجان الوفاء - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2009)

محطات في تاريخ بلدة القرارة (الحلقة الأولى: زمن التأسيس) - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2009)

خصائص تفسير الشيخ إبراهيم بن عمر بيوض - الوزناجي, نادية (الحياة, 2009)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981)

البعد العقدي والحضاري للفن (قراءة تحليلية في فكر بيجوفيتش ومالك بن نبي) - بابا عمي, محمد بن موسى (الحياة, 2009)

تحية الجزائر لسلطنة عمان - باجو, صالح بن إبراهيم (الحياة, 2009)

القضايا الوطنية والعربية والإسلامية من منظور أعلام ميزاب (1902-1962) - بن عمر, موسى بن بكير (الحياة, 2009)
Keywords: Biographies – Mzab – 20e siècle

الافتتاحية - بن يحيى, يحيى بن صالح (الحياة, 2009)

المضمون الإسلامي في الشعر الجزائري الحديث - بوحجام, محمد بن قاسم ناصر (الحياة, 2009)
Keywords: Poésie – Mzab

محمد عاشق السواد…! (نثر) - بوحجام, محمد بن قاسم ناصر (الحياة, 2009)

الحماية القانونية المتميِّزة للأملاك الوقفية في الجزائر - بوراس, عيسى بن محمد (الحياة, 2009)
Keywords: Waqf (fondations) – Mzab

في الذكرى العشرين لرحيل شيخ الشباب وشاب الشيوخ (الشيخ إبراهيم قرادي) - حاج أمحمد, يحيى بن بهون (الحياة, 2009)

فصل في الفصل بين عبد الله بن إباض الحيادي والمحكمة ... (الحلقة الأولى) - حريزي, موسى بن إبراهيم (الحياة, 2009)

فقه المال العام عند الإباضية (الحلقة الثالثة: عند فقهاء إباضية المشرق) - حمدي, محمد بن صالح (الحياة, 2009)
Keywords: Fiqh

مقياس "علم الاجتماع الإسلامي" في الجامعة الجزائرية .... - خواجة, عبد العزيز بن محمد (الحياة, 2009)

التعليم القرآني في الزوايا والمدارس القرآنية بين الواقع والمأمول... - دفرور, رابح (الحياة, 2009)
Keywords: Enseignement – Mzab

اعتراف بالمقام - زيد الخير, مبروك (الحياة, 2009)

خطاب الشيخ إبراهيم بن عمر بيوض في مؤتمر قدماء التلاميذ بغرداية (مؤرخ بـ 29/11/1373 - 29/07/1954) - شريفي, سعيد بن بالحاج (الحياة, 2009)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981)

قراءة سوسيو-أخلاقية لمنظومة قيم التدريس - مرموري, بشير بن عمر (الحياة, 2009)
Keywords: Enseignement – Mzab

إصلاح الأنفس بالقرآن وليس بتغيير الإنسان - ناصر, محمد صالح (الحياة, 2009)
Keywords: Développement personnel – Aspect religieux

Ouargla : Bientôt une nouvelle maison de l'artisanat - Alioua, Houria (El Watan, 2009)
La maison de l'artisanat de Ouargla, avenue de la République, à Ouargla, a fermé ses portes pour se refaire une beauté. Même si ces travaux de réfection tombent mal avec ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

« Ce qui se passe à Ghardaïa c'est le printemps noir bis » - Aït Mouhoub, Zahir (El Watan, 2009)
De l'arrestation des militants FFS à Ghardaïa aux alternatives de changement du système politique, Karim Tabbou brosse pour El Watan Vendredi un tableau peu optimiste de la chose politique algérienne ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Mohamed Baba Nedjar condamné à perpétuité : Retour sur un procès singulier - Bouaricha, Nadjia (El Watan, 2009)
Regards hagards, mines défaites, l'assistance, qui a assisté au procès de Mohamed Baba Nedjar, semble étonnée par le verdict prononcé par le juge. « Mais sur quelle base a-t-il ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Ghardaïa : Le FFS dénonce des intimidations policières - Bouaricha, Nadjia (El Watan, 2009)
La fédération de Ghardaïa du Front des forces socialistes (FFS) a dénoncé hier « le retour des intimidations policières contre les militants du parti ». Mettant « ces pressions » dans le contexte du procès ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Kamel Eddine Fekhar (Initiateur de l'appel pour l'officialisation du rite ibadite) - Bouaricha, Nadjia (El Watan, 2009)
Se sentant victimes de leur situation minoritaire, les ibadites réclament l'officialisation de ce rite afin de parer à toute menace ou agression. Kamel Eddine Fekhar, militant des droits de l ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Fekhar et les 15 militants du FFS relaxés - Makedhi, Madjid (El Watan, 2009)
Heureuse issue pour le fédéral du FFS à Ghardaïa, Kamel Eddine Fekhar, et les 15 autres militants du parti. Le tribunal de Ghardaïa a prononcé, jeudi dernier, leur acquittement. Seule une ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Ghardaïa Le procès des deux militants du FFS reporté - Kachemad, L. (Liberté (Algérie) (site web), 2009)
Le procès des deux militants du FFS, accusés de l'incendie en 2004 d'un véhicule appartenant au Croissant-Rouge algérien de la commune de Ghardaïa, s'est déroulé. Très tôt ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Kamel Fekhar dénonce l'injustice - N. B. (El Watan, 2009)
Deux militants et cadres de la fédération de Ghardaïa du Front des forces socialistes (FFS) comparaîtront aujourd'hui devant le tribunal de Ghardaïa pour répondre de l'accusation « d'incendie d ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Ghardaïa : La LADDH dénonce une atteinte au rite ibadite - N. B. (El Watan, 2009)
Le bureau de la Ligue algérienne de défense des droits de l'homme (LADDH) de la wilaya de Ghardaïa a dénoncé, hier, à travers un communiqué, l'installation d'une « commission ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Ghardaïa : Kamel Fekhar exige la levée du contrôle judiciaire - Bouaricha, Nadjia (El Watan, 2009)
Le docteur Kamel Eddine Fekhar, militant des droits de l'homme et membre de la direction du Front des forces socialistes, a décidé de faire appel suite à la décision du ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Ghardaïa Kamel Eddine Fekhar placé sous contrôle judiciaire - Kachemad, L. (Liberté (Algérie) (site web), 2009)
Ce n'est que vers 19h, mardi et après toute la journée passée dans l'enceinte du tribunal de Ghardaïa, que le docteur Kamel Eddine Fekhar a été libéré. Selon son ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Suite à des plaintes déposées par des commerçants Kamel-Eddine Fekhar et le vice-président de l'APC de Ghardaïa interpellés par la police - Kachemad, L. (Liberté (Algérie) (site web), 2009)
Le responsable de la fédération du FFS de Ghardaïa et membre de la direction du parti, le docteur Kamel-Eddine Fekhar, a été arrêté, lundi après-midi, par des policiers en ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Kamel Eddine Fekhar et 4 autres militants du FFS arrêtés par la police - Bouaricha, Nadjia (El Watan, 2009)
Dans un communiqué rendu public hier, le Front des forces socialistes a fait état de l'arrestation, hier, de cinq militants du parti à Ghardaïa, dont le docteur Kamel Eddine Fekhar ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Après la condamnation de baba nedjar à perpétuité Ghardaïa : le FFS appelle les commerçants à une grève - Kachemad, L. (Liberté (Algérie) (site web), 2009)
Dans un communiqué parvenu à notre bureau de Ghardaïa, portant la signature du docteur Kamel-Eddine Fekhar, responsable de la Fédération du Front des forces socialistes de Ghardaïa, une analyse rétrospective ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

À la veille du procès de mohamed Baba nedjar de ghardaïa Le FFS dénonce les pressions et intimidations - Kachemad, L. (Liberté (Algérie) (site web), 2009)
La fédération FFS de Ghardaïa estime que son militant est victime d'une cabale. Dans un long communiqué parvenu à notre bureau de Ghardaïa, la fédération de Ghardaïa du Front des ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Faut-il officialiser le rite ibadite ? - Meddi, Adlène (El Watan, 2009)
Alors que le ministre d'Etat, Abdelaziz Belkhadem, plaidait l'implantation « sur tout le territoire national » du rite malékite, mardi lors d'un colloque à Aïn Defla, et déclarait que « le ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Les ibadites demandent l'officialisation de leur rite - M. A. O. (El Watan, 2009)
Le rite ibadite « doit » être officialisé. Des milliers de citoyens - de Ghardaïa - le revendiquent et le font savoir à travers une lettre adressée aux plus hauts responsables de l'Etat dont ...
Keywords: Fekhar; Kamel Eddine (1963-2019)

Et Krystian rencontra Ben Laden: Allemand d'origine polonaise, le principal accusé du procès de l'attentat de Djerba s'est converti à l'islam en 1986. Il clame son innocence - Bordenave, Yves (Le Monde, 2009)
Keywords: Attentats – Djerba – 2002

Djerba : le lieutenant présumé de Ben Laden se dit innocent - Durand Souffland, Stéphane (Le Figaro, 2009)
Keywords: Attentats – Djerba – 2002

Figures de Midoun : Said Doghri 1881-1935 entre finances et solidarité - S.T. (La Presse Magazine, 2009)
Keywords: Biographies – Djerba – 20e siècle

Trois hommes jugés à Paris pour l'attentat de Djerba (Le Monde, 2009)
Keywords: Attentats – Djerba – 2002

Al-Qaïda en procès à Paris. Les auteurs présumés de l'attentat de Djerba, en mars 2003, seront jugés lundi à Paris (Paris-Normandie, 2009)
Keywords: Attentats – Djerba – 2002

Le professeur Slaheddine Tlatli nous a quittés - S.R. (La Presse Magazine, 2009)

Djerba La Douce - Claivaz, Pascal (Le Nouvelliste, 2009)
Keywords: Tourisme – Djerba

Les complices de l’attentat de Djerba nient tout - Tomasovitch, Geoffroy (Aujourd’hui en France, 2009)
Keywords: Attentats – Djerba – 2002

Les complices de l’attentat de Djerba jugés à Paris - Tomasovitch, Geoffroy (Aujourd’hui en France, 2009)
Keywords: Attentats – Djerba – 2002

Changement climatique : vulnérabilité de Djerba et nécessaire adaptation - Damergi, J. (L’Économiste Maghrébin, 2009)
Keywords: Crises environnementales – Djerba

Escapade - Trabelsi, Salem (La Presse Magazine, 2009)
p. I : Midoun : Le souk autour de l’olivier p. II-IV : Un site exceptionnel pour le développement du tourisme p. III : Mokhtar Mandra : Au grain... la « Zomita » p. VI : « Ouled Jemaa » : la fête par le « gougou » p. VI : Architecture : Un coup de cœur sur la route p. VII : Said Doghri 1881-1935 : Entre finances et solidarité p. VIII : Un nouveau plan touristique pour Midoun. Interview de M. Abdelwaheb Majoul (Président du syndicat d’initiative du tourisme) à Djerba-Midoun.
Keywords: Tourisme – Djerba

Terrorisme : Attentats de Djerba : les liens du sang - Ghorbal, Sami (Jeune Afrique, 2009)
Keywords: Attentats – Djerba – 2002

Le musée du patrimoine traditionnel de Djerba: un nouveau type de musée - Ben Hadid, Taoufik (Archibat, 2009)
Keywords: Architecture – Djerba

Marianne Catzaras des images à l'inquiétante étrangeté - Belhassine, Olfa (Archibat, 2009)
Keywords: Architecture – Djerba

Tahar M'guedmini, couleurs émotions - Belhassine, Olfa (Archibat, 2009)
Keywords: Architecture – Djerba

Chaouat : Terres cuites de Djerba : « J’ai cherché des poètes, j’ai trouvé des potiers » (G. Duhamel) - Belhassine, Olfa (tunizien, 2009)
Keywords: Artisanat – Djerba

L'empire des Djerbiens, existe-t-il encore ? (Le blog de successtory, 2009)
Voici une liste de succes story d'anciens promoteurs Djerbien, la question est, existent-t-ils de nouveaux investisseurs qui sont aptent à protéger ce chemin de succès? La famille Ben Yedder, qui possède un empire avec des ramifications dans la banque...
Keywords: Commerce – Djerba

المساجد في جربة التونسية .. تتزين بالأبيض والأخضر وتتخفف من الزخرفة (صحيفة الاقتصادية, 2009)
المساجد في جربة التونسية .. تتزين بالأبيض والأخضر وتتخفف من الزخرفة
Keywords: Architecture – Djerba

Djerba ou Ulysse résistant au chant des sirènes ! - Karoui, Hatem (www.tunisietoday.com, 2009)

Tunisie: Gestion des déchets - Alerte rouge à Djerba - Haouari, Imen (La Presse, 2009)
Keywords: Crises environnementales – Djerba

Djerba et la presqu'île de Zarzis face au changement climatique - Bouabid, Naceur (Turess, 2009)
Library Catalog: www.turess.com

La mosquée séculaire de Boulimane à Djerba recouvre son minaret - Bouabid, Naceur (Turess, 2009)
Library Catalog: www.turess.com
Keywords: Architecture – Djerba; Bûlaymân; Mosquée (Ja’bîra; Djerba); Monuments – Djerba

Djerba, paradis en détresse - Maamer, Kérim (Jeune Afrique, 2009)
Keywords: Crises environnementales – Djerba

بلاد الجريد: تراث إنساني عريق - بوترعة, جهينة (الحياة الثقافية, 2009)
Place: تونس
Keywords: Architecture – Nefta

هندسة المعمار في مدينة الجريد: تراث ثقافي وحضاري جدير بالدراسة والبحث - نصيري, الأخضر (الحياة الثقافية, 2009)
Place: تونس
Keywords: Architecture – Nefta

الدر المنتخب في الفقه والأدب - الخروصي, سعيد بن خلف (2009)

جذور الحركة النسائية بتونس روايات لشخصيات تاريخية, النقل إلى العربية الفصحى عروسية النالوتي - العبيدي, ليليا (مطبعة تونس قرطاج, 2009)
Keywords: Littérature

رسالة في بعض أعراف وعادات وادي مزاب - القرادي, أيوب بن إبراهيم (جمعية النهضة, 2009)

‏رسالة في حكم التجويد القرآن وتلاوته - لعلي, صالح بن عمر بن داود (2009)
Keywords: Coran – récitations

الآراء الكلامية لأبي یعقوب الوارجلاني رسالة ماجستير في اصول الدين - خبزي, دليلة (مكتبة مسقط, 2009)
Keywords: Foi – Traité – 12e siècle

ترميم المعمار العامي جامع "ولحي" بجربة نموذجا - الطبجي بن رجب, نجوى (كلية العلوم الإنسانية والإجتماعية, 2009)
Keywords: Monuments – Djerba; Walḥī; mosquée (Oued Zbib; Djerba)

‏فهرس مخطوطات ⁨خزانة دار التلاميد (إروان) بجامع غرداية الكبير: ‏اقدام واكبر خزانة مخطوطات بمدينة غرداية - الحاج موسى, بشير بن موسى (مؤسسة الشيخ عمي سعيد, 2009)
Keywords: Bibliothèques – Mzab; Catalogue – Mzab; Manuscrits – Mzab

The Mosques of Djerba Les Mosquées de Djerba - Hallet, Stanley Ira; Djerbi, Ali (Les Editions de l'Université de Carthage, 2009)
Keywords: Architecture – Djerba; Monuments – Djerba; Tâjdît; Mosquée (Fâtû; Djerba)

Islam and the Culture of the State in Oman - Tsibiridou, Fotini (2009)

Ethnoarchaeology Research in the Sultanate of Oman (Ras al-Hadd) - Efstratiou, Nikolaos (2009)
Keywords: Archéologie – Oman

Berber Majority Ibadhi Minority in North Africa : Ibadhi community in Libya (Nafousa), Tunisia (Djerba) and Algeria (Mzab) - Umādī, Mūḥammad (2009)
Keywords: Berbérisme – Djebel Nefousa; Berbérisme – Djerba; Berbérisme – Mzab

Study-Groups and the practice od Ibadhism in an Omani town - Limbert, Mandana E. (2009)

A Political Culture and Foreign Policy Shaped by a Moderate Religious View: The Case of the Sultanate of Oman - Rabi, Uzi (2009)
Keywords: Vie politique – Oman – 1970-2020

Ibadism and Omani Nation-Building since 1970 - Valeri, Marc (2009)
Keywords: Vie politique – Oman – 1970-2020

The Modern Face of Ibadism in Oman - Eickelman, Dale F. (2009)
Keywords: Ibadisme – Oman

Historical Memories and Imagined Communities. Modern Ibadi Writings on Khārijism - Hoffman, Valerie J. (2009)
Keywords: Kharijisme

Terminologies ibadites, présentation d'un dictionnaire par un co-auteur - Baḥḥāz, Ibrāhīm (2009)

The juridical perception of Ibadhism - Patragas, Kyriakos Nikolaou (2009)
Keywords: Fiqh

The formation and early development of the Ibāḍī madhhab - Francesca, Ersilia (2009)
Keywords: Fiqh

Theological trends in early Ibadism epistles - Sayyid, Ridwan al- (2009)

‘Abd Allāh Ibn Yazīd al-Fazārī on the Abode of Islam - Madelung, Wilferd (2009)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Ibadism. Some Reconsiderations of its Origins and Early Development - Wilkinson, John Craven (2009)

General introduction: Ibadi Studies until now - Ess, Josef van (2009)

‏مسائل الإيمان بالله تعالى عند الإمام إبراهيم بن عمر بيوض من خلال تفسيره في رحاب القرآن - حمدي, صالح بن محمد (دار الخلدونية, 2009)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Coran – Commentaires – 20e siècle

Le Recueil Authentique De La Tradition Prophétique - Rabi' ibn Habib al- (2009)
Keywords: Hadith – recueils

The Letters of Jābir bin Zayd (d.93H) - Mamari, Mohamed Said al- (2009)
Keywords: Fiqh

Review of In the Shadow of the Ancestors. The Prehistoric Foundations of the Early Arabian Civilization in Oman - Lombard, Pierre (Paléorient, 2009)
Keywords: Recension

Jeffrey T. Kenney, Muslim Rebels: Kharijites and the Politics of Extremism in Egypt (Oxford: Oxford University Press, 2006). Pp. 234. $45.00 cloth. - Kalmbach, Hilary (International Journal of Middle East Studies, 2009)
Keywords: Recension

Bernardie-Tahir, Nathalie (dir.) (2008) L’autre Zanzibar. Géographie d’une contre-insularité. Paris, Karthala, 379 p. (ISBN 978-2-84586-946-2) - Bouchard, Christian (Cahiers de géographie du Québec, 2009)
Un article de la revue Cahiers de géographie du Québec, diffusée par la plateforme Érudit.
Keywords: Recension

ديوان الشيخ عامر بن سليمان الشعيبي - الشعيبي, عامر بن سليمان (وزارة التراث والثقافة, 2009)

علاقة الرستميين بالإمارة الأموية في الأندلس - بوباية, عبد القادر (التراث العربي, 2009)
Keywords: Relations – Tahert – Andalousie

الىزعة الوحدوية في شعر "مفدي زكرياء" - الوحدة الوطنية والمغاربية أنموذجا - - بوتومـي, ليندة; تومي, مسعودة (جامعة يحي فارس, 2009)
Keywords: Poésie – Mzab

قيام نظام الإمامة في عمان (1331 - 1339هـ / 1913 - 1920م) - التركي, عبد الله بن إبراهيم (مجلة جامعة أم القرى لعلوم الشريعة والدراسات الاسلامية, 2009)
يهدف هذا البحث إلى دراسة عودة نظام الإمامة في عمان، وظهوره كقوة منافسة للسلطان العماني، ومناوأة للنفوذ البريطاني في المنطقة. \ فمنذ توقيع معاهدة الحماية بين سلطنة عمان وحكومة الهند البريطانية عام 1308 هـ/1891 م تحولت العلاقة بين الجانبين إلى حكم غير مباشر من قبل بريطانيا لعمان، عبر الوكيل السياسي والقنصل البريطاني في مسقط، فتم منع تجارة الرقيق وتجارة السلاح. وتحت ذريعة مقاومة تلك التجارتين، تم تضييق الخناق علي القبائل العمانية وتم تدمير كثير من سفنها التجارية، وفي المقابل تم منح الرعايا البريطانيين مزيداً من الحرية والمميزات. \ أدت تلك الإجراءات إلى تجمع القبائل العمانية ومعظمها من القبائل الأباضية. وتم انتخاب إمام من بينهم وذلك عام 1331هـ/ 1913م، وتشكلت حكومة محلية داخل عمان، ونقضت هذه القبائل بيعتها للسلطان، وأنشأت قوة عسكرية استطاعت أن تستولي بها علي معظم المناطق العمانية سوى بعض الموانئ المهمة مثل: مسقط، ومطرح. \ ومن هنا تدخلت بريطانيا إلى جانب السلطان فيصل بن تركي ثم إلى جانب ابنه تيمور بن فيصل وذلك بالدعم المادي والعسكري، ثم تدخلت بوساطة بين الإمام والسلطان وعقدت عدة لقاءات بين الجانبين أسفرت عن توقيع اتفاقية السيب عام 1339 هـ/ 1920م وبموجب ذلك انقسمت عمان، ففي الداخل يحكم الإمام، وفي الساحل يحكم السلطان. \ يهدف هذا البحث * إلى دراسة عودة نظام الإمامة (1) في عمان وظهوره كقوة منافسة للسلطان العماني ومناوأة للنفوذ البريطاني في المنطقة، ومحاولة تلمس الأسباب التي أدت إلى نجاحه كقوة داخلية استطاعت أن تستقطب عدداً كبيراً من القبائل العمانية وذلك في العقد الرابع من القرن الرابع عشر الهجري، العقد الثاني من القرن العشرين الميلادي، ثم تتبع مراحل نزاع الإمامة مع السلطان العماني حتى تم توقيع اتفاقية السيب (2) عام 1339 هـ/ 1920 م بين السلطنة العمانية والإمامة الأباضية (3) بوساطة بريطانية، والجديد الذي تضيفه هذه الدراسة أنها تعتمد علي وثائق عربية وإنجليزية جديدة من أرشيف وزارة الهند في لندن، إضافة إلى عدد من المصادر العربية والأجنبية الأخرى \
Keywords: Vie politique – Oman – 1913-1932

Mediterranean islands in Tabula Peutingeriana - Pazarli, Maria (e-Perimetron, 2009)
Keywords: Cartes – Djerba

The Iron Age ceramic tradition in the Gulf: a re-evaluation from the Omani perspective - Iamoni, Marco (Proceedings of the Seminar for Arabian Studies, 2009)
Keywords: Archéologie – Oman

Debating Slavery and Abolition in the Arab Middle East - Ghazal, Amal N. (Slavery, Islam and diaspora, 2009)
Keywords: Esclavage – Zanzibar

Rituals of Royalty and the Elaboration of Ceremony in Oman: View from the Edge - Chatty, Dawn (International Journal of Middle East Studies, 2009)

اختالف المطالع وأثره على اختالف األهلة - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2009)

Retention of the passive verb in a Bedouin dialect of northern Oman - Eades, Domenyk (Zeitschrift Für Arabische Linguistik, 2009)
The present contribution examines the form and function of the apophonic ("internal") passive (AP) in an Arabic dialect of northern Oman. The AP is one of several features common to all the dialects of Oman, having been retained in dialects of both the "Bedouin" (B) and "sedentary" (S) types. In a study of the AP in dialects of Oman and eastern Arabia, Clive Holes (1998) showed that this category survives as a functioning marker of the passive voice in Omani S dialects mostly in the historically isolated interior of the country, albeit in verbs belonging to a restricted set of syntactic and lexicosemantic categories. The purpose of the present study is to determine whether the same process of recession has taken place in a B dialect of the Omani interior. Results of the study reveal that in the B dialect of the Hidyīwī tribe, whose dīra is located in the hinterland of Muḍaybi in northern Oman, the AP is significantly more productive than in the S dialects described by Holes. This contrast corresponds with certain socio-historical factors which distinguish the different speech communities of the interior. In particular, the Hidyīwī community is significantly more isolated from outsider contact and maintains a more homogeneous, tight-knit social structure than towns in which the S dialects are spoken.
Keywords: Linguistique – Oman

الحرف العمانية: دراسة توثيقـية - السيابية, عائشة بنت خلفان (الهيئة العامة للصناعات الحرفية, 2009)

Libyan Berbers struggle to assert their identity online - Rumi, Aisha al- (Arab Media & Society, 2009)
Keywords: Berbérisme – Libye

الشيخ غالب بن علي الهنائي (Alwasat News, 2009)
Keywords: Biographies – Oman

العلاقات العمانية الفرنسية (1741-1810)م - عمر, باسمة عبد العزيز (مجلة الخليج العربي, 2009)
During the eighteenth century, the Arabian Gulf region had witnessed a great European competition and, due to its strategic location on the way to India, sultanate of Oman had felt such competition between England and France to have its ally and to be preferred, and due to the increase of such competition between England and France, Muscat thought that it is preferable to be idle in its relation with the two competitive powers at that time. In spite of that, the first roller of Albu-Said family, Ahmed bin Said (1741-1783) knew the benefit of the French friendship, the relation between Muscat and France had not developed to the level of diplomatic one but only a trade relation because England was competing them. However Muscat relations with France took a developed phase with Sultan bin Ahmed while he was rolling Muscat. He got benefit from the English - French competition to build a good relation with France in 1796, in addition to the predominant trade relations. Such action had its influence on England, which forced the Sultan to sign an agreement on 1800, rejecting some of the facilities which had been given to France before, and the English occupation of Morrishious Island (the main French Colony in the Indian Ocean), ended the French dreams in extending their power and finished a phase of a hesitated Omani-French relations.
Keywords: Relations – Oman – France

From Stinkibar to Zanzibar': Disease, Medicine and Public Health in Colonial Urban Zanzibar, 1870-1963 - Issa, Amina A. (University of KwaZulu-Natal, 2009)
Keywords: Zanzibar

Ghardaïa : la Mecque des architectes (Bladi Algérie, 2009)
Keywords: Architecture – Mzab

Le négoce de matières premières de Zanzibar et les affaires commerciales des négociants Kutchs et Occidentaux - Goswami, Chhaya (Synergies Inde, 2009)
Au dix-neuvième siècle, l’île de Zanzibar connut une intense activité commerciale (esclavage, ivoire, clous de girofle, tabac, noix de coco…). L’article montre la concurrence entre principales nations : France, Angleterre, Allemagne, Etats-Unis et Inde et montre comment cette dernière s’empara progressivement du marché.
Keywords: Zanzibar

Un’altra Storia. Le Memorie di Mohamed Fekini, patriota libico - Greppi, Carlo (I Sentieri della Ricerca, 2009)

Mouvements de population et mutations sociales: réflexions sur la gestion des entrées et des sorties dans les Cités du M’zab - Oussedik, Fatma (2009)
Keywords: Urbanisme – Mzab

أبعاد الرمز الديني التاريخي عند مفدي زكرياء: إلياذة الجزائر أنموذجا - بن حاج الطاهر, فاطمة; طوير, حفيظة (جامعة الدكتور يحي فارس, 2009)
Keywords: Poésie – Mzab

الصحيفة القحطانية - ابن رزيق, حميد بن محمد بن بخيت (Ministry of Heritage and Culture, 2009)
Keywords: Sources – Oman

الصحيفة القحطانية - ابن رزيق, حميد بن محمد بن بخيت (Ministry of Heritage and Culture, 2009)
Keywords: Sources – Oman

الصحيفة القحطانية - ابن رزيق, حميد بن محمد بن بخيت (Ministry of Heritage and Culture, 2009)
Keywords: Sources – Oman

الصحيفة القحطانية - ابن رزيق, حميد بن محمد بن بخيت (Ministry of Heritage and Culture, 2009)
Keywords: Sources – Oman

الصحيفة القحطانية - ابن رزيق, حميد بن محمد بن بخيت (Ministry of Heritage and Culture, 2009)
Keywords: Sources – Oman

Water Management: the use of stars in Oman - Nash, Harriet (University of Exeter, 2009)

أدب الأطفال عند محمد ناصر - دومان, غنية (جامعة الحاج لخضر, 2009)
Keywords: Littérature – Mzab

Race, revolution, and the struggle for human rights in Zanzibar: the memoirs of Ali Sultan Issa and Seif Sharif Hamad - Burgess, G. Thomas; Issa, Ali Sultan; Hamad, Seif Sharif (Ohio University Press, 2009)
Keywords: Zanzibar

Fonctionnement du hydraulique de partage de la palmeraie Est de Ghardaïa - Djoudi, Hakima; Rafa, Amina (Ecole Nationale Supérieure Polytechnique, 2009)

الشيخ القرادي الحاج أيوب إبراهيم بن يحيى 1923-1989م: آثاره الفكرية - حاج أمحمد, يحيى بن بهون (جمعية النهضة, 2009)
Keywords: Biographies

الشيخ القرادي الحاج أيوب إبراهيم بن يحيى 1923-1989م: التأبين والتعازي - حاج أمحمد, يحيى بن بهون (جمعية النهضة, 2009)
Keywords: Biographies

الشيخ القرادي الحاج أيوب إبراهيم بن يحيى 1923-1989م: رسالة في بعض أعراف وعادات وادي مزاب - حاج أمحمد, يحيى بن بهون (جمغية النهضة, 2009)
Keywords: Biographies

تقييد وبيان من عمر في وادي ميزاب لمحمد بن الخيذر بن أحمد بن يوسف الملياني تحقيق - إيعيش, جميلة (جامعة الجزائر, 2009)

Emerging Identities in Colonial Tunisia: "Alliancist" and Zionist Representations in Tunis prior to World War I - Land, Joy (University of Connecticut, 2009)
Keywords: Judaïsme – Djerba

L'art comme réappropriation du monde - Attia, Kader; Boulbina, Seloua Luste (Cahiers Sens public, 2009)
Keywords: Urbanisme – Mzab

Visiting a Dead Mother: Algeria 1930 - Bendahan, Blanche (Women Writing Africa : the Northern Region, 2009)
Keywords: Judaïsme – Mzab

Rapport sur Yafran (libyawatanona, 2009)
مجموعة تاويزا للعمل الامازيغي الليبي

تقرير حول يفرن (libyawatanona, 2009)
مجموعة تاويزا للعمل الامازيغي الليبي

Britain and the Gulf: At the Periphery of Empire - Peterson, John E. (The Persian Gulf in history, 2009)
Keywords: Vie politique – Oman – 1970-2020

Life after Oil: Economic Alternatives for the Arab Gulf States - Peterson, John E. (Mediterranean Quarterly, 2009)
Keywords: Vie politique – Oman – 1970-2020

Mirroring Modernity: on consumerism in cosmopolitan Zanzibar - Prestholdt, Jeremy (Transforming Cultures eJournal, 2009)
This essay develops an image of nineteenth century Zanzibari consumer sensibilities by demonstrating how goods from and new engagements with distant locales affected the socio-cultural landscape of Zanzibar. The East African port’s particular cosmopolitanism represents one form of social reconstitution stimulated by global integration. It also represents a material vision of global relations that was discounted by nineteenth century theorizations of Western modernity. By focusing on the rise of a new materiality in Zanzibar, I excavate precolonial visions of global relations and cultural assimilations of global symbols. I argue that East African desires for goods produced all over the globe represented not simply a Westernization, Indicization, or Arabization of Zanzibar, but also a reconfiguration of a standardized set of global materials in an attempt to bring Zanzibari cultural forms into conversation with broader global trends.
Keywords: Zanzibar

‏أثر السيرة النبوية في بناء قصيدة مفدي زكريا أنموذجا - ملوج, نادية; بوزرقولة, فاطمة (جامعة يحي فارس, 2009)
Keywords: Poésie – Mzab

Bir İbadî Çocuk İlmihali “Telkînü's-Sıbyan" - Ateş, Orhan (e-Makalat Mezhep Araştırmaları Dergisi, 2009)
Bir mezhebin fikirlerinin doğru anlaşılmasında kendi kaynakları oldukça önemlidir. İbâdîler'in itikadi görüşleri hakkında az sayıda çalışma yapılmış olmakla beraber İbâdî ilmihali hakkında ülkemizde herhangi bir çalışma mevcut değildir. Bu açıdan makaleye konu olan Telkinü's-Sıbyân isimli ilmihali önemsemekteyiz. Telkinü's-Sıbyân İbâdîler arasında tanınan bir kaynaktır ve Umman'da yaz tatillerinde İbâdî çocuklar bu kitabı okumaktadır. İlk kısmı İbâdî itikadı diğer bölümler ise ibadetlere ayrılmıştır. Bu sayede İbâdî itikadını ve namaz konusundaki farklı uygulamalarını kendi kaynaklarından öğrenmiş olacağız

Le coton et l'Islam: fil d'une histoire africaine - Philiponeau, Marie (Casbah éditions, 2009)

دور الاتصال في إدارة الأزمات كارثة فيضانات غرداية (2008) أنموذجا (دراسة ميدانية) - بوهاني, فطيمة (جامعة الجزائر, 2009)
Keywords: Inondations – Mzab – 2008

التقليد والتجديد عند أبي اليقظان - تواتي, نوال; العروي, سميحة; دريادي, آسية (جامعة الدكتور يحي فارس, 2009)

رواية الفرقة الناجية : المنطق والتحليل - العدوي, خميس بن راشد (مكتبة الغبيراء, 2009)

Caractérisation génétique des isolats berbérophones du Sud tunisien par confrontation des résultats de trois marqueurs polymorphes - Fadhlaoui-Zid, Karima; Sanchez-Mazas, Alicia; Buhler, Stéphane; Khodjet-Elkhil, Houssein; Ben Amor, Mohamed; Comas, David; Dugoujon, Jean-Michel; Slama, Hmida; Benammar Elgaaied, Amel (Antropo, 2009)
In this study, we are interested to polymorphism of three genetic markers (GM Allotypes, HLA Classe II and mtDNA) in three Berber isolates (Chenini-Douiret, Matmata and Sened) localed in the South of Tunisia. Our objective is to evaluate the genetic impact of the invasions which Tunisia has knew after the Berber settlement by considering genetic diversity of these three isolates and by comparing these Berber populations to other North-African populations.
Keywords: Génétique – Afrique du Nord

Sortie du livre, d’Ahmed Bakelli : De l’histoire des Ibadites au Maghreb - M'Hamsadji, Kaddour (2009)
Keywords: Littérature – Mzab

Les Juifs d'Afrique du Nord - Bibliographie : Supplément à l’édition de 1993 - Attal, Robert (2009)
Keywords: Judaïsme – Djerba

التنافس البريطانى الفرنسى للسيطرة على عمان 1888-1904: دراسة وثائقية - الأسدي, رياض جاسم محمد (الوثيقة, 2009)
Keywords: Vie politique – Oman – 1888–1913

Mapinduzi Daima – Revolution Forever: Using the 1964 Revolution in Nationalistic Political Discourses in Zanzibar - Suhonen, Riikka (University of Helsinki, 2009)
Keywords: Zanzibar

Rembrandt in Oman - Schmierer, Richard J. (US Embassy, 2009)
Keywords: Vie culturelle – Oman

Oman: Jewish engagement - Schmierer, Richard J. (US Embassy, 2009)
Keywords: Judaïsme – Oman

The Omani and Bahraini paths to development: rare and contrasting oil-based economic success stories - Looney, Robert (Unu-Wider, 2009)
Oman and Bahrain are Middle Eastern success stories. There are some key similarities. Both have followed pragmatic development strategies built on a stable foundation of strengthened governance structures and enhanced economic liberalization. These improvements occurred in somewhat different settings, with Oman developing in a more authoritarian environment, whereas Bahrain enjoyed greater democracy but somewhat less stability. While both countries have relied on oil revenues to support their development efforts, it appears that, in contrast to their less successful oil producing neighbours, each country had just enough oil to do some good, but not enough to do serious damage. – Oman ; Bahrain ; Middle East ; GCC ; economic development ; economic growth ; development strategies
Keywords: Pétrole – Oman

La spécificité du Mali sur l'échiquier africain - Djiré, Salif Mandela (Université Paris 8, 2009)

L'immigration subsaharienne au Maghreb : le cas libyen - Ghileb, Salim (Université Paris 8, 2009)

Oman - Religion and Society through American Eyes - Grazda, Edward (Ministry of Endowments & Religious Affairs, 2009)
Keywords: Récits de voyage – Oman

الكتابات في المساجد العمانية القديمة - Baldissera, Eros (وزارة التراث القومي والثقافة, 2009)
Keywords: Archéologie – Oman

Ghardaia, Ideological and Cultural Oasis - Pearce, David D. (US Embassy, 2009)
Keywords: Moeurs et coutumes – Mzab

Politics Rattle the Tunisian-American Chamber of Commerce - Godek, Robert F. (US Embassy, 2009)
Keywords: Barouni; Mohamed Moncef

Ambassador Visits Jewish Community in Djerba - Godek, Robert F. (US Embassy, 2009)
Keywords: Judaïsme – Djerba

End of the Road, the Last Imam of Oman Dies, But... - Hurtado, L. Victor (US Embassy, 2009)
Keywords: Hinai; Ghalib bin Ali al- (1913-2009)

Irregular Forces in Counterinsurgency Warfare - Clegg, Will (Security Challenges, 2009)
Keywords: Dhofar

“Our Mother is Afro-Shirazi, Our Father is the Revolution”: The 1964 Zanzibar Revolution in Tanzanian History - Daly, Samuel (Columbia University, 2009)
Keywords: Zanzibar

Oman and the Franco-British Colonial Rivalry: The Bandar al-Jissah Crisis 1898-1900 - Ghailany, Yusuf A. M. al- (مجلة آداب, 2009)
Keywords: Vie politique – Oman – 1888–1913

التعليم في سلطنة عمان في ظل الخطة الخمسيت الثانية 1985-1981 - ياسين, سبلة طلال (دراسات تاريخية, 2009)
Keywords: Enseignement – Oman

Abolition de l'esclavage dans le Sahara Algérien - Daddi Addoun, Yacine (University of Toronto, 2009)
Keywords: Esclavage – Algérie

Traditional Arts in Southern Arabia: Music and Society in Sohar, Sultanate of Oman - Christensen, Dieter; El-Shawan Castelo-Branc, Salwa (Verlag für Wissenschaft und Bildun, 2009)
Keywords: Musique – Oman

تركيبة مجتمع مدينة الجزائر خلال العهد العثماني (1519-1830) - جماعة بني ميزاب أنموذجا - - الزرويل, صالح (المركز الجامعي بغرداية, 2009)
Keywords: Emigration – Mzab – Algérie; Mzab – Histoire – 1510-1830

Etude expérimentale du trouble atmosphérique sur le site de Ghardaïa - Benkaciali, S.; Gairaa, K. (Revue des Energies Renouvelables, 2009)
Ce travail présente une étude qualitative et quantitative du trouble atmosphérique au site de Ghardaïa. Il s’agit de la détermination du facteur de trouble de Linke T*L, à partir des mesures instantanées données par une station radio métrique, qui utilise un système de poursuite à trois dimensions. Les mesures effectuées ont permis de déterminer ce coefficient, et de prédire sa variation annuelle et mensuelle qui présente un maximum au moi d’août (l’absorption par la vapeur d’eau est importante et une faible diffusion par les aérosols) et aussi une valeur importante du trouble au mois de juin (forte diffusion par les grains de sables), et un minimum en hiver (faible absorption par la vapeur d’eau et faible diffusion par les aérosols), à l’exception d’une période courte des tempêtes de sable (entre Mars et Mai) où la diffusion des aérosols grain de sable est prépondérante. D’après notre étude et nos observations sur site, on a constaté qu’il y a deux saisons principales à Ghardaïa (chevauchement des deux saisons).

This holy seed - Daniel, Robin (Tamarisk Publications, 2009)
Keywords: Donatisme

مسند الربيع بن حبيب (الجامع الصحيح عند الإباضية) : دراسة نقدية - السالك, عبد الرحمن أحمد (الجامعة الأردنية, 2009)
Keywords: Hadith – Exégèse

الإمامة عند الإباضية - الوائلي, ناصر بن سالم (جامعة القديس, 2009)

An island through time: Jerba studies - Fentress, Elizabeth; Drine, Ali; Holod, Renata; Aït Kaci, Ahmed (Journal of Roman Archaeology, 2009)
Keywords: Archéologie – Djerba; Monuments – Djerba; Sidi Garus; mosquée (Haddada; Djerba); Sidi Jmur; mosquée (El Groo; Djerba)

آراء عبد اللّه بن يزيد الفزاري الكلامية - الصخراوي, فوزي (كلية العلوم الانسانية والاجتماعية, 2009)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

The early Kharijites and their understanding of Jihad - Lahoud, Nelly (Mélanges de l’Université Saint-Joseph, 2009)
Keywords: Kharijisme

سير الوسياني - الوسياني, سليمان بن عبد السلام (وزارة التراث والثقافة, 2009)
Wisyānī, Abū ‘l-Rabīʿ Sul. b. ʿAbd al-Sallām b. Ḥassān al-: Siyar al-Wisyānī li-Abī ‘l-Rabīʿ Sul. b. ʿAbd al-Sallām b. Ḥassān al-Wisyānī (Q 6 H./12 M.). Ed. ʿUmar b. Luqmān Ḥammū Sul. Būʿaṣbāna. 3 vols. Muscat: MHC, 1430/2009, (vol. 1, pp. 1-530; vol. 2, pp. 517 (sic)-946; vol. 3, pp. 942 (sic)-1235; 24x17 cm.).*
Keywords: Jaddi Isa; mosquée (Robbana; Djerba); Jami al-Kabir; mosquée al- (Hachene; Djerba); Monuments – Djerba

سير الوسياني - الوسياني, سليمان بن عبد السلام (وزارة التراث والثقافة, 2009)
Wisyānī, Abū ‘l-Rabīʿ Sul. b. ʿAbd al-Sallām b. Ḥassān al-: Siyar al-Wisyānī li-Abī ‘l-Rabīʿ Sul. b. ʿAbd al-Sallām b. Ḥassān al-Wisyānī (Q 6 H./12 M.). Ed. ʿUmar b. Luqmān Ḥammū Sul. Būʿaṣbāna. 3 vols. Muscat: MHC, 1430/2009, (vol. 1, pp. 1-530; vol. 2, pp. 517 (sic)-946; vol. 3, pp. 942 (sic)-1235; 24x17 cm.).*
Keywords: Abu Muhammad Kammus; mosquée (Hachene; Djerba); Abu Zakariyya Fasil; mosquée (Bani Bandou; Djerba); Jaddi Isa; mosquée (Robbana; Djerba); Jami al-Kabir; mosquée al- (Hachene; Djerba); Monuments – Djerba

The Latest on the Archaeology of Southern Oman - Zarins, Juris (Journal of the American Oriental Society, 2009)
Keywords: Archéologie – Oman

The Hawari of Socotra, Yemen - van Rensburg, Julian Jansen (The International Journal of Nautical Archaeology, 2009)
Haw ̄ar ̄ı are traditionally logboats carved from a single tree into a double-ended vessel which can be propelled by either sails or paddle. Haw ̄ar ̄ı can be found throughout the Indian Ocean from India through to East Africa, yet little is known about this ubiquitous vessel. The aims of this research are to address this lacuna in our knowledge by documenting the rich source of haw ̄ar ̄ı present on the island of Socotra, Yemen.
Keywords: Archéologie – Oman

Kharijites - Sonn, Tamara; Farrar, Adam (Oxford Bibliographies, 2009)
Keywords: Kharijisme

al-Dawla al-ʿUthmāniyya wa dawr al-Inkishāriyya (Inkishāriyyat Jarba Namūdhajan) - Inkishārī, al-Hādī b. Yūsuf b. Muḥammad al- (al-Maṭbaʿa al-Rasmiyya lil-Jumhūriyya al-Tūnisiyya, 2009)

Oman: politics and society in the Qaboos state - Valeri, Marc (Hurst, 2009)
Keywords: Vie politique – Oman – 1970-2020

Sefer Shirat ha-ḳodesh shel nashim meha-I G'erba shebe-Tunisyah - Guez-Avigal, Miriam (Orot Yahadut ha-Magrab, 2009)
“Poésie de prophètes”: le chant sacré des juives de l’île de Djerba en Tunisie
Keywords: Judaïsme – Djerba

The Jews of Djerba - Greenspan, Ari (Mishpacha, 2009)
Keywords: Judaïsme – Djerba

Les lieux de la revitalisation du judaïsme aujourd’hui. Vers un brouillage des frontières entre ashkénazes et séfarades ? - Endelstein, Lucine (Archives Juives, 2009)
Keywords: Judaïsme – Djerba

De Tunis, à Djerba, confiscations et pillages - Danan, Ariel (Les Cahiers du judaïsme, 2009)
Keywords: Judaïsme – Djerba

Al-aṣwāt al-muhammašaẗ: al-h̲udūʻ wa-ʻiṣyān fī Lībiyā at̲nāʾ al-istiʻmār wa-baʻdahu - Ahmida, Ali Abdullatif (Markaz Dirāsāt al-Waḥda al-ʻarabiyyaẗ, 2009)
Keywords: Italie – colonies

Review : Hoffmann-Ruf, Michaela: Scheich Muhsin bin Zahrän al-'Abri. Tribale Macht im Oman des 19. Jahrhunderts. Berlin (Klaus Schwarz) 2008. 46 Euro. ISBN 978-3-97997-353-8. - Lohlker, Rüdiger (Wiener Zeitschrift für die Kunde des Morgenlandes, 2009)
Keywords: Recension

Tourismus der Rückkehr als kulturelle Reserve: jüdische Pilger aus Frankreich auf dem Weg nach Djerba und zurück - Peveling, Barbara (Zeitschrift für Ethnologie, 2009)
JewishpilgrimsareyearlyvisitingtheGhriba Synagogueon the islandofDjerba in spring time. This pilgrimage offers for the social Jewish actors an opportunity to revitalize their oriental iden tity,which has been trailed away as consequence of theirmigration to Europe. For the local Muslims in Djerba the Jewish pilgrims renew the memories of the past local Jewish community. The touristic rite means a local resistance in the global interpretation of Jewish-Muslim relations, overshadowed by the Palestinian Conflict.
Keywords: Judaïsme – Djerba; Tourisme – Djerba

Princess of Zinj - Shipman, John (2009)
British-Yemeni Society
FMC
Keywords: Zanzibar

Sīrat Mashāyikh Nafūsa - Bughṭūrī, Maqrīn b. Muḥammad al- (Tawalt, 2009)
Keywords: Prosopographie – Djebel Nefousa

min al-Riḥlāt al-Ḥijāziyya li-ʿUlamā’ al-Maghrib al-Islāmī - Ḥājj Amḥammad, Yaḥyā b. Buhūn (2009)
FMC

“Do you not fear God?” The Khawārij in early Islamic history - Sizgorich, Thomas N. (Violence and belief in late antiquity: militant devotion in Christianity and Islam, 2009)
Keywords: Kharijisme

Fatḥ al-Abwāb ilà Sullam al-Iʿrāb. Ta’līf al-Shaykh al-ʿAllāma Ḥabīb b. Yūsuf al-Fārisī (1276-1329) - Fārisī, Ḥabīb b. Yūsuf al- (Ministry of Heritage and Culture, 2009)

al-Durr al-Manẓūm fī Dhikr Maḥāsin al-Amṣār wa’l-Rusūm. Riḥlat Ḥammūd al-Būsaʿīdī, 1872, al-Ḥijāz - Miṣr - al-Shām - Būsaʿīdī, Ḥamūd b. Aḥmad al- (al-Takwīn li’l-Ta’līf wa’l-Tarjama wa’l-Nashr, 2009)

Takhlīṣ al-ʿĀnī min Raqabat Jahl al-Maʿānī - Iṭfayyish, Muḥammad b. Yūsuf (Ministry of Heritage and Culture, 2009)

Kitāb al-Adilla wa’l-Bayān - Malshūṭī, Tibghūrīn b. ʿĪsà b. Dāwud al- (Ministry of Heritage and Culture, 2009)
Keywords: Foi – Traité – 12e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-

al-Imām Nāṣir b. Murshid al-Yaʿrabī. Dirāsa Tārīkhiyya fī Nihāyat al-Dawla al-Nabhāniyya wa-Bidāyat al-Dawla al-Yaʿrabiyya - Manāṣir, Ṭāriq al- (Makt. Al-Ḍāmirī, 2009)
Keywords: Biographies – Oman

al-Shaykh al-ʿAllāma Yaḥyà b. Khalfān b. Abī Nabhān al-Kharūṣī wa-Ishāmātuhu li’l-Maktaba al-ʿUmāniyya (1227-1322H./1812-1905 M.). - Kharūṣī, Khālid b. ʿAbdallāh. b. Sayf al- (2009)
Keywords: Biographies – Oman

Review : Traditional Arts in Southern Arabia: Music and Society in Sohar, Sultanate of Oman - Urkevich, Lisa (The World of Music, 2009)
Keywords: Recension

La guerre du Dhofar, 1965-1976: un modèle de contre-rébellion - Morin, Tony (Centre de doctrine d'emploi des forces, 2009)
La guerre du Dhofar se déroulant dans le sultanant d'Oman et engageant des troupes britanniques entre 1965 et 1976 illustre une réussite peu connue de contre-rébellion, car menée dans la discrétion et intégrant complètement actions civiles et militaires.
Keywords: Dhofar

Vocabulaire grammatical amazighe = Amawal n tjerrumt - Ameur, Meftaha; Bounfour, Abdellah (Institut royal de la culture amazighe, 2009)
Keywords: Linguistique

Zinjibār, Shakhṣiyyāt wa-Aḥdāth, 1828-1972 - Riyāmī, Nāṣir b. ʿAbdallāh al- (Dār al-Ḥikma, 2009)
Keywords: Zanzibar

al-Ṣiḥāfah al-ʻUmānīyah al-muhājirah: ṣaḥīfat al-Falaq wa-shakhṣīyātuhā: al-Shaykh Hāshil ibn Rāshid al-Muskarī namūdhajan - Kindī, Muḥsin (Riyāḍ al-Rayyis lil-Kutub wa-al-Nashr, 2009)
Keywords: Journalisme – Oman

al-Khawārij. Nash’atuhum, Firaquhum, Ṣifātuhum, al-Radd ʿalà Abraz ʿAqā’idihim - Ghuṣn, Sulaymān b. Ṣāliḥ (Dār Kunūz Ishbīliyā li’l-Nashr wa’l-Tawzīʿ, 2009)
Keywords: Kharijisme

Manhaj al-Kitāba al-Tārīkhiyya ʿinda ‘l-ʿAwtabī - Zarmān, Muḥammad (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Uṣūl al-Manhaj al-ʿAqadī ʿinda ‘l-ʿAwtabī fī Kitābihi al-Ḍiyā’ - Wahībī, Muslim b. Sālim al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Dirāsa Tawthīqiyya li-Turāth al-ʿAwtabī al-Makhṭūṭ - Shaybānī, Sulṭān b. Mubārak (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Manhaj al-ʿAwtabī fī Kitābihi al-Ḍiyā’ - Sharīfayni, Muḥammad ʿĪsà al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Qaḍāyā al-Lugha wa-Jamāliyyātuhā fī K. al-Ḍiyā’ li’l-ʿAwtabī al-Ṣuḥārī - Shalabī, Ṭāriq (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Juhūd al-ʿAwtabī fī ‘l-Fikr al-Islāmī (Namādhij min Fiqh al-ʿAwtabī al-Mālī: Dirāsa Muqārana) - Samīrān, Muḥammad ʿAlī (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Fiqh

al-Shawāhid al-Shiʿriyya fī K. al-Ibāna li’l-ʿAwtabī - Riḍwānī, Maḥmūd al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Poésie – Oman

Asālīb Qirā’at al-Naṣṣ al-Shiʿrī ʿinda ‘l-ʿAwtabī al-Ṣuḥārī al-ʿUmānī fī Kitābihi al-Ibāna fī ‘l-Lugha al-ʿArabiyya - Quḍāt, Bathīna al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Poésie – Oman

al-Muṣṭalaḥ al-Ṣawtī ʿinda ‘l-ʿAwtabī al-Ṣuḥārī fī K. al-Ibāna - Qarāla, Zayd al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Taqʿīd al-Fiqhī ʿinda ‘l-ʿAwtabī - Qarāla, Aḥmad; ʿAbd al-Ḥamīd, Muḥammad (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Fiqh

Manhaj al-ʿAwtabī fī ‘l-Ta’līf fī K. al-Ibāna fī ‘l-Lugha al-ʿArabiyya: al-Ḥaqīqa wa’l-Majāz Un-mūdhajan - Marāshida, ʿAbd al-Bāsiṭ (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Dars al-Dallālī ʿinda ‘l-Imām Salma b. Muslim al-ʿAwtabī al-Ṣuḥārī - Maqbūl, Idrīs (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-ʿAwtabī Mu’arrikhan - Manāṣir, Muḥammad al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Mudawwanāt al-Fiqhiyya Maṣdaran li-Tārīkh ʿUmān al-Ijtimāʿī fī ‘l-ʿUṣūr al-Islāmiyya: K. al-Ḍiyā’ li’l-ʿAwtabī al-Ṣuḥārī Unmūdhajan - Zawāhira, ʿUmar Khalaf al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Fiqh

Naẓarāt fī Taḥqīq K. al-Ibāna li’l-ʿAwtabī - Zubaydī, Saʿīd Jāsim al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Majlis al-ʿAwtabī - Maʿmarī, Ḥamad b. Hilāl al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Malmaḥ al-Balāghī fī K. al-Ibāna - Kitāna, Ḥusayn; Rāshidī, ʿUmar al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Manhaj al-ʿAwtabī fī ‘l-Sunna wa-ʿUlūmihā - Kindī, Aḥmad al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Isti’nāf al-Naẓar al-Kalāmī ladà ‘l-ʿAllāma al-ʿAwtabī - Jūl, Muḥammad Zāhid (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Ṣiyagh al-Taʿajjub fī K. al-Ibāna li’l-ʿAwtabī - Jarrār, Ṣalāḥ (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Mabāḥith al-Naḥwiyya fī K. al-Ibāna li’l-ʿAwtabī - Jarrār, ʿAbd al-Rāziq Fāliḥ (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Milkiyyat al-Arḍ wa’l-Ḍarā’ib fī ʿUmān mundhu al-Fatḥ al-Islāmī wa-ḥattà al-Qarn al-sādis al-Hijrī/al-thānī ʿashar al-Mīlādī Istinādan ilà ‘l-Maṣadir al-Fiqhiyya al-Ibāḍiyya - Jālūdī, ʿUlayyān (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Fiqh

Athār al-Fuqāha fī K. al-Ibāna li’l-ʿAwtabī - Ismāʿīl, Sayyid ʿAlī (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Archéologie – Oman

Manhaj al-ʿAwtabī al-Fiqhī min khilāl K. al-Ḍiyā’ - ʿIbrī, Saʿīd b. ʿAbdallāh al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Fiqh

al-Amthāl fī K. al-Ibāna li’l-ʿAwtabī al-Ṣuḥārī: Dirāsa Taḥlīliyya - Ḥarāḥasha, Aḥmad al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Riwāya fī ‘l-Ta’līf ʿinda ‘l-ʿAwtabī (Akhbār Imru’ al-Qays Unmūdhajan) - Ḥarāḥasha, Aḥmad al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Naẓarāt fī K. al-Ansāb li’l-ʿAwtabī (al-Manhaj wa’l-Uslūb) - Ḥammūda, Ḥanān (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Mushāhada ḥawla ‘l-ʿAwtabī: Naẓra Istiʿrāḍiyya Naqdiyya - Fawzī, Fārūq ʿUmar (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Mathal ʿinda ‘l-ʿAwtabī: K. al-Ibāna Shāhidan - Darrūbī, Muḥammad al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Juhūd al-ʿAwtabī fī ‘l-Fikr al-Islāmī - Būsaʿīdī, Ṣāliḥ b. Aḥmad b. Sayf al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Juhūd al-Lughawiyya li’l-ʿAwtabī wa-Qīmatuhā al-ʿIlmiyya - Būqāʿī, Muḥammad al-Yanbaʿī al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Linguistique – Oman

Dawr al-ʿUmāniyyīn fī Futūḥ al-Shām wa’l-ʿIrāq min khilāl K. al-Ansāb li’l-ʿAwtabī (Qays b. Hubayra al-Makshūḥ Unmūdhajan) - Banī Khālid, Mūsà (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-ʿAllāma al-ʿAwtabī al-Ṣuḥārī wa-Fuṣūl min Fiqh al-Lugha - Ballāsī, Muḥammad (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Fiqh

Ishāmāt al-ʿAwtabī fī Mabāḥith ʿUlūm al-Qur’ān - Shaykh Bālḥājj, Qāsim b. Aḥmad al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

ʿAmr b. Maʿdī Karib al-Zubaydī wa-Dawruhu fī Futūḥ al-ʿIrāq wa-Bilād Fāris min khilāl K. al-Ansāb li’l-ʿAwtabī - ʿAzzām, ʿĪsà al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Biographies; Sources – Oman

Talaqqī al-Khiṭāb al-Balāghī fī K. al-Ibāna li’l-ʿAwtabī - ʿAwda, Amīn (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

al-Ibāna ʿan Manhaj al-ʿAwtabī fī Kitābihi “al-Ibāna fī ‘l-Lugha al-ʿArabiyya” - ʿAmrī, Laylà Tawfīq al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Linguistique – Oman

Qabā’il al-Azd wa-Imtidāduhā qabla ‘l-Islām wa-baʿdahu kamā yuʿakkisuhā K. al-Ansāb li’l-ʿAwtabī al-Ṣuḥārī - Aḥmad, Nahla Aḥm. ʿAbd al-Bāqī (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Maṣādir al-ʿAwtabī fī ‘l-Tafsīr - Abū Khaḍir, Saʿīd Jabr (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Coran – Commentaires

Aḍwā’ Lisāniyya ʿalà “al-Tawāṣul al-Lughawī wa-Muqawwimātuhu” fī K. al-Ibāna li’l-ʿAwtabī - Abū Khaḍir, Saʿīd Jabr (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)

Kitāb al-Ansāb li’l-ʿAwtabī al-Ṣuḥārī - Abū Dāwud, Sāmī Ṣaqr (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār (Māris) 2008, 2009)
Keywords: Généalogie – Oman

al-Balāgha ʿinda ‘l-ʿAwtabī fī K. al-Ibāna - Abū ʿAlūsh, Ibrāhīm Muḥammad (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār(Māris) 2008, 2009)
Keywords: Linguistique – Oman

Nakabāt al-Mahāliba wa-Maṣīr Nisā’ihim fī ʿAṣr al-Dawla al-Umawiyya (86-102 H./705-720 M.) kamā ṣawwarahā al-ʿAwtabī al-Ṣuḥārī fī Kitābihi al-Ansāb - Abū ‘l-ʿAlā, Ibrāhīm ʿAbd al-Munʿim (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār(Māris) 2008, 2009)

al-ʿAwtabī wa-Talaqqī al-Shiʿr al-Jāhilī fī K. al-Ibāna - ʿAbsī, Muḥammad al- (al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār(Māris) 2008, 2009)
Keywords: Poésie – Oman

al-ʿAwtabī al-Ṣuḥārī. Awrāq al-Nadwa al-Duwaliyya allatī naẓẓamahā Waḥdat al-Dirāsāt al-ʿUmāniyya fī Jāmiʿat Āl al-Bayt bi’l-Taʿāwun maʿa Sifārat Salṭanat ʿUmān al-Shaqīqa fī ‘l-Mamlaka al-Urdunniyya al-Hāshimiyya bi-Tārīkh 16-17 Rab. I 1429 H./24-25 Ādhār(Māris) 2008 - Jālūdī, ʿUlayyān; Abū Khaḍir, Saʿīd Jabr (Jāmiʿat Āl al-Bayt, 2009)

al-Tārīkh wa-al-bayān fī ansāb qabāʼil ʻUmān - Hināʼī, Maddād ibn Saʻīd ibn Ḥamd (Dār al-Ḥikmah, 2009)

Safar al-Manẓūmāt. Dirāsa Taḥlīliyya Tārīkhiyya li-Manẓūmat al-Jawhar wa’l-ʿAraḍ ʿinda Abī Bakr Aḥm. b. ʿAbdallāh. al-Kindī al-mutawaffà 557 H. - Maʿmarī, ʿAbdallāh. al- (Mu’assassat al-Intishār al-ʿArabī, 2009)

al-Khawārij fī ‘l-Tārīkh wa’l-Siyāsa wa’l-Fiqh wa-ʿIlm al-Kalām wa’l-Khuṭab wa’l-Shiʿr wa’l-Ṭarā’if - Farḥāt, Amīra (Dār al-Maḥajja al-Bayḍā’, 2009)
Keywords: Kharijisme

Oceano indiano occidentale: scorci di storia - Nicolini, Beatrice (Polimetrica, 2009)
Keywords: Zanzibar

al-Awḍā’ al-Siyāsiyya wa’l-Iqtiṣādiyya fī Salṭanat Masqaṭ wa-Atharuhā ʿalà ‘l-Milāḥa wa’l-Tijāra fī ʿAhd al-Sulṭān Turkī b. Saʿīd wa-Ibnihi Fayṣal, 1873-1914. Dirāsa Wathā’iqiyya - Bassām, ʿAlī b. Ḥusayn b. ʿAbdallāh. al- (al-Dār al-ʿArabiyya li’l-Mawsūʿāt, 2009)
Keywords: Vie politique – Oman – 1871-1888

Dirāsāt fī Tārīkh al-ʿAlāqāt al-Faransiyya al-ʿUmāniyya fī ‘l-ʿAṣr al-Ḥadīth - ʿAzzāwī, Muḥammad ʿAbdallāh (al-Dār al-Waṭaniyya al-Jadīda, 2009)
Keywords: Relations – Oman – France

تجارة عمان الخارجية عبر العصور التاريخية - عزيزي, أحمد (مركز الراية للنشر والإعلام, 2009)
ʿAzīzī, Aḥm. b. ʿAbdl. b. Masʿūd al-: (2009) Tijārat ʿUmān al-Khārijiyya ʿabra ‘l-ʿUṣūr al-Tārīkhiyya. Cairo: Markaz al-Rāya li’l-Nashr wa’l-Iʿlām, 2007, (191 pp., 24x17 cm.). ISBN 977.354.148.7.*

Lemmes en berbère ancien provenant d’un glossaire berbéro-arabe et d’une œuvre ibâḍite-berbère médiévale - Ould-Braham, Ouahmi (Études et Documents Berbères, 2009)
Keywords: Linguistique

The Wajīhids of Oman - Salimi, Abdulrahman al- (Proceedings of the Seminar for Arabian Studies, 2009)
The downfall of the first Omani imamate in 280/885 represented the beginning of clashes between Ibāḍī ideology and the emerging family dynasties in different Omani provinces. The dynastic rulers sought to abolish the imamate system in the country, which led to serious conflict between distinguished political families and Ibāḍī scholars. Perhaps Wajīhid's reign in the fourth/tenth century symbolizes this best. This important family's rule of the country brought about fundamental changes in the areas of politics and commerce, which in turn has occupied the interest of many historians and archaeologists. This paper focuses on the emergence of the Wajīhid, their relations with Omani Ibāḍīs, and the subsequent political and economical changes in Oman. Finally, the paper examines this development in relation to the centre of the caliphate in Baghdad, the Būyids and Qarmatians (Carmathians).
Keywords: Archéologie – Oman

Tourisme et Qualité Environnementale. Parcours de qualité pour la filière touristique de l’île de Djerba - Corsale, Andrea; Sistu, Giovanni (Nuove Grafiche Puddu, 2009)
Keywords: Tourisme – Djerba

Perception du manque d’eau par la population djerbienne (Tunisie) - Hamzi, Amina (Université Paris 8, 2009)

الإمام محمد بن محبوب الرحيلي :‏ ‏حياته وآثاره :‏ تحقيق كتاب أبواب من السنة مختصرة - الرحيلي, محمد بن محبوب (وزارة التراث والثقافة, 2009)
Bābazīz, Sul. b. Ibr. [Bābazīz] al-Wārijlānī: (ed.) (2009b) al-Imām Muḥ. b. Maḥbūb al-Rahīlī: Ḥayātuh wa-Āthāruhu (t. 260 H.). Taḥqīq K. Abwāb min al-Sunna Mukhtaṣaratan. Muscat: MHC, 1430/2009, (338 pp., 24x17 cm.).*

الرسالة الحجة لأئمة المسلمين :‏ ‏رسالة الربيع بن حبيب ومخلد بن العمرد و وائل في: مسائل اجتهادية و فتنة النكار - الفراهيدي, الربيع بن حبيب; ابن أيوب, وائل; بن العمرد, مخلد (وزارة التراث والثقافة, 2009)
al-Risāla al-Ḥujja. Risālat al- Rabīʿ b. Ḥabīb wa-Makhlad b. ʿUmurrud wa-Wā’il b. Ayyūb wa-Jamāʿat al-Muslimīn fī: * Masā’il al-Khilāf allatī kānat bi’l-Mashriq: - fī Ḥukm Ṣalāt al-Jumʿa; -al-Mar’a allatī atat bi-shibh Zinā; - al-Qawl fī ‘l-Muta’awwilīn li’l-Tashbīh. * al-Khilāf alladhī kāna bi’l-Maghrib: - Fitnat al-Nukkār.
Keywords: Nukkarisme

الهجرات العمانية إلى شرق إفريقيا في القرن الهجري الأول و الرابع و السابع :‏ ‏دراسة سياسية و حضارية - النعماني, سعيد بن سالم (‏جامعة القاهرة, 2009)

المعتمد في فقه الكفارات :‏ ‏من آراء الشيخين الجليلين أحمد بن حمد الخليلي و سعيد بن مبروك القنوبي حفظهم الله تعالى، مسائل في الكفارات المرسلة، الكفارات المغلظة، الكفارات المختلف فيها - المعولي, المعتصم بن سعيد (مكتبة وتسجيلات الهلال الاسلامية, 2009)
Keywords: Fiqh; Fiqh – Oman – 2000-....

كتاب المعلقات في أخبار و روايات أهل الدعوة - بابزيز, سليمان بن إبراهيم (وزارة التراث والثقافة, 2009)
Anonymous: K. al-Muʿallaqāt fī Akhbār wa-Riwāyāt Ahl al-Daʿwa. Ed. Sul. b. Ibrāhīm Bābazīz al-Wārijlānī. Muscat: MHC, 1430/2009, (398 pp., 24,5x17,5 cm.).
Keywords: Bin Ya'lâ; mosquée (Erriadh; Djerba); Jaddi Isa; mosquée (Robbana; Djerba); Monuments – Djerba; Prosopographie – Djerba

الشيخ سعيد بن خلفان الخليلي وآراؤه الكلامية - الغافري, عبدالله بن سعيد (‏جامعة القديس يوسف, 2009)

السنة: الوحي و الحكمة قراءة في نصوص المدرسة الإباضية - العدوي, خميس بن راشد; المحرمي, زكريا بن خليفة; الوهيبي, خالد بن مبارك (مكتبة الغبيراء, 2009)

القواعد الفقهية عند الإباضية: تنظيرا و تطبيقا - الراشدي, هلال بن محمد (مركز الغندور, 2009)
Keywords: Fiqh

المجموعة الراشدية - الراشدي, سعيد بن حمد (المعد, 2009)

سيرة العلامة القاضي الشيخ سيف بن حماد بن أحمد الخروصي 1313-1379 - الخروصي, خالد بن عبد الله (2009)

الإمام أبو حمزه الشاري: حياة من أجل الحق - الجعبيري, فرحات بن علي (مكتبة الضامري, 2009)
Jaʿbīrī, Farḥāt al-: (2009) al-Imām Abū Ḥamza al-Shārī. Ḥayāt min ajl al-Ḥaqq. Al-Sīb: Makt. Al-Ḍāmirī, 1430/2009, (186 pp., 24x17 cm.).* Jaabiri Farhat

تأملات في التاريخ السياسي العماني - حمودي, هادي حسن (بيت العلم, 2009)
Keywords: Vie politique – Oman

سير الوسياني - الوسياني, سليمان بن عبد السلام (وزارة التراث والثقافة, 2009)
Wisyānī, Abū ‘l-Rabīʿ Sul. b. ʿAbd al-Sallām b. Ḥassān al-: Siyar al-Wisyānī li-Abī ‘l-Rabīʿ Sul. b. ʿAbd al-Sallām b. Ḥassān al-Wisyānī (Q 6 H./12 M.). Ed. ʿUmar b. Luqmān Ḥammū Sul. Būʿaṣbāna. 3 vols. Muscat: MHC, 1430/2009, (vol. 1, pp. 1-530; vol. 2, pp. 517 (sic)-946; vol. 3, pp. 942 (sic)-1235; 24x17 cm.).*
Keywords: Abu Muhammad Kammus; mosquée (Hachene; Djerba); Jaddi Isa; mosquée (Robbana; Djerba); Jami al-Kabir; mosquée al- (Hachene; Djerba); Monuments – Djerba; Sidi Salih; mosquée (Bani Bandou; Djerba)

في رحاب القرآن :‏ ‏مختصر تفسير العلامة الشيخ بيوض (من سورة الجاثية إلى آخر سورة المجادلة) برواية ورش عن نافع - بيوض, إبراهيم بن عمر (وزارة التراث والثقافة, 2009)
Keywords: Coran – Commentaires – 20e siècle

ديوان الأشياخ (كتاب البيوع)، بحث في التّاريخ الإقتصادي لجنوب إفريقيّة خلال القرنين الخامس والسّادس الهجريين/11-12م - بن غازي, البشير (كلية العلوم الانسانية والاجتماعية, 2009)
Keywords: Fiqh – Traité – 11e siècle

محفل الطبالة بجزيرة جربة بين الموسيقى والحركة الجسدية - الشويخي, وليد (المعهد العالي للموسيقى بسوسة, 2009)
Keywords: Musique – Djerba

العقليات والقوالب النمطية دراسة في مفهوم السياحة الثقافية بجزيرة جربة - بن قيراط, محسن (المعهد العالي للتنشيط الشبابي و الثقافي, 2009)
Keywords: Tourisme – Djerba

مفاهيم الاحتكار في الاقتصاد المعاصر ومستجداتها - الجعبيري, فرحات‏ بن علي (أعمال ندوة تطور العلوم الفقهية - فقه التوقع, 2009)
Jaabiri
Keywords: Fiqh

الخوارج واراؤهم الإقتصادية (مجلة كلية التربية, 2009)
Keywords: Kharijisme

الرثاء بين الشيعة والخوارج في العصر الأموي - القتم, عبد الله (المجلة العربية للعلوم الإنسانية, 2009)
Keywords: Kharijisme

الكتابة التاريخية عند الخوارج في بلاد المغرب في القرنين الرابع والخامس الهجري - حسن, آمال محمد; شكيران, محمد عبدالكريم (صحيفة دار العلوم للغة العربية وآدابها والدراسات الإسلامية, 2009)
Keywords: Kharijisme

The Coinage of Obayda b. Al-Muhager Amir Al-Mu minin Al-khawarej in Iraq 256H 870 AD - Ramdan, Atef Mansour M. (أدوماتو, 2009)
عبيدة بن المهاجر من أتباع مساور الخارجي الذي ثار بالموصل ضد الخلافة العباسية. وقد حدث خلاف في عقيدة الخوارج بين مساور وعبيدة، واقتتلا بسبب ذلك، وانتهي الأمر بمقتل عبيدة على يد مساور. ولم تذكر المصادر التاريخية معلومات كافية عن هذه الحادثة، ولكن النقود- التي تعد مصدراً مهماً من مصادر التاريخ الإسلامي- ألقت الضوء عليها، من خلال درهمين نادرين باسم عبيدة ضرب نصيبين سنة 206ه، لم يسبق نشرهما أو دراستهما من قبل. وهما النموذجان الوحيدان المعروفان على مستوي العالم لهذا الخارجي؛ الأول محفوظ بمركز المسكوكات الإسلامية بجامعة توبنجن بألمانيا، والثاني كان ضمن مجموعة الدكتور اليش لوتز بألمانيا، ثم انتقل إلى ملكية جمعية النميات الأمريكية بنيويورك سنة 1987م.
Keywords: Numismatique – Irak

Réflexions sur la révolte des berbères kharijites au Maghreb sous le gouvernement de Umar b. Hafs (151-154 / 768-771) une relecture des sources textuelles à la lumière des source numismatiques - Fenina, Abdelhamid (المجلة التونسية للعلوم الاجتماعية, 2009)
La révolte des Berbères kharijites sous le gouvernement de cUmar b. Hafs (151-154/768-771), objet de la présente étude, est relativement bien connue dans l’historiographie de l’Ifrîqiya. Toutefois, nous observons que les récits de nos chroniqueurs, dont aucun n’est contemporain des faits relatés, fourmillent d’informations tantôt confuses tantôt contradictoires. De fait, la chronologie de la révolte et certains autres faits historiques restent encore difficiles à discerner. Afin de contribuer à une meilleure connaissance de cet épisode obscur de l’histoire du Maghreb au milieu du IIe /VIIIe siècle, nous avons essayé de confronter les données recueillies dans nos sources textuelles aux témoignages numismatiques, contemporains des faits. Cette approche, nous a permis de proposer à la fois une relecture de certains faits rapportés par nos sources narratives et une chronologie de la révolte.
Keywords: Numismatique

أحكام وقف المسجد في المذهب الإباضي: دراسة مقارنة بقانون الأوقاف العماني - الزريقي, جمعة محمود (الندوة الدولية: الوقف في عمان بين الماضي والحاضر, 2009)
Keywords: Waqf (fondations) – Oman

مصادر الفقه الإباضي في القرنين الثالث والرابع الهجري - البراشدي, صالح بن خلفان (جامعة الزيتونة, 2009)
Keywords: Fiqh

حقيقة الوقف ومشروعيته - الحراصي, سلطان بن محمد بن زهران (الندوة الدولية: الوقف في عمان بين الماضي والحاضر, 2009)
Keywords: Waqf (fondations) – Oman

مسند الربيع بن حبيب الإباضي : دراسة نقدية - آل حميد, سعد بن عبدالله بن عبدالعزيز (مجلة جامعة أم القرى لعلوم الشريعة والدراسات الاسلامية, 2009)
الإباضية إحدى الفرق الإسلامية التي كانت تعتمد في استدلالها من السنة على كتب الحديث المعروفة عند أهل السنة، ولم يكن يعرف لهم كتاب في الحديث إلا في القرون المتأخرة ؛ حين ظهر لهم كتاب " الجامع الصحيح ؛ مسند الربيع بن حبيب " الذي يقولون: إنه أصح الكتب بعد القرآن. ولكن هذا الكتاب لا يصح؛ لعدة أسباب، منها: ا) أنه ليس له أصل خطي يوثق به. 2) جهالة مرتبه الوارجلاني، وليس للكتاب إسناد إلى الوارجلاني، ولا بين الوارجلاني والربيع بن حبيب. 3) جهالة الربيع بن حبيب، وشيخه أبي عبيدة مسلم بن أبي كريمة 4) الانقطاع بين أبي عبيدة وجابر بن زيد؛ لعدم الدليل على تتلمذ أبي عبيدة على جابر بن زيد. 5) وجود الانقطاع والانقطاع الشديد في كثير من أسانيد الكتاب العليا؛ من الربيع فمن فوقه. 6) لم يظهر الكتاب في عصر الرواية والنقد، ولم يستدل الإباضية القدامى بأحاديثه فيما يعتقدونه مما يخالفون فيه غيرهم. 7) اعتذر متأخرو الإباضية عن عدم ظهور الكتاب لعلماء الحديث ؛ بالخوف من بطش الحكومات، فاعترض عليه بوجود فرصة لظهوره وقت قيام الدولة الرستمية الإباضية التي حكمت أكثر من ثلاثين ومئة سنة. 8) تفرد هذا الكتاب بأحاديث تضمنت أحكاما شرعية تحتاجها الأمة، ويحرص على معرفتها علماء الحديث، فلو كانت مرونة آنذاك لما غابت معرفتها عن علماء الحديث، بالإضافة لعدد آخر من الأحاديث المعارضة لأحاديث صحيحة، والله أعلم \
Keywords: Hadith – Exégèse

مدخل إلى دراسة الإباضية وعقيدتها : بحث مقارن في اللاهوت الإباضي في بلاد المغرب وعمان - Cuperly, Pierre (مكتبة المشكاة, 2009)

الإسلام السياسي من الخوارج إلى المنطقة الخضراء - المشهداني, سعدون (دار ورد للنشر والتوزيع, 2009)
Keywords: Kharijisme

الدولة العثمانية ودور الانكشارية: إنكشارية جربة نموذجا - الإنكشاري, الهادي بن يونس (نشر المؤلف, 2009)

تغوري دصح: كلمة أمازيغية معناها الطين الصافي وهي ترمز إلى كل شيء أصيل ونقي ومعدنه جيد: مجموعة شعرية - فارس, نورالدين (2009)
Keywords: Littérature – Djerba

تاريخ جربة وعلمائها الأباضية - بن يعقوب, سالم (2009)
Ibn Yaʿqūb, Sālim: (2009) Tārīkh Jarba wa-ʿUlamā’ihā al-Ibāḍiyya. Tunis: no publisher, 1430/2009, (364 pp., 24x16 cm.).*
Keywords: Monuments – Djerba; Sidī Yaʿīsh; mosquée (Jaabira; Djerba); Walḥī; mosquée (Oued Zbib; Djerba)

L’évaluation de l’image d’une ville. Cas de la ville de Djerba - Maïrech, Mohamed Aymen (Faculté des Sciences Economiques et de Gestion de Tunis, 2009)
Keywords: Tourisme – Djerba

De l'histoire des ibadites au Maghreb. Regard libre sur les chroniques d'Abou Zakaria - Bakelli, Ahmed (Casbah éditions, 2009)
Keywords: Littérature – Mzab

الاستدلال على قضايا العقيدة عند ناصر بن أبي نبهان الخروصي (ت 1262 ھ/ 1846 م) - الحجري, سلطان بن عبيد (التفاهم, 2009)

المذهب الذَرّي الكلامي عند أبي بكر الكندي العُماني - المعمري, عبد الله (التفاهم, 2009)

La valorisation du patrimoine vecteur de développement local durable : quelles retombées économiques et quel dispositif institutionnel ? Cas du Sud-Est tunisien - Abichou, Hanane (Université Montpellier I, 2009)
Keywords: Développement local – Djerba

Pluralismo e convivenza: Djerba, il caso degli ultimi “ebrei arabi” - Parodi da Passano, G. (Pluralismo religioso e modelli di convivenza: atti del Convegno di Torino, 20-21 settembre 2006, 2009)
Keywords: Judaïsme – Djerba

Rabah NABLI, Les Entrepreneurs tunisiens. La difficile émergence d’un nouvel acteur - Ferréol, Gilles (Revue européenne des migrations internationales, 2009)
Keywords: Recension

Décret n° 2009-1228 du 20 Avril 2009, relatif à l'approbation du contrat de concession de la réalisation et de l'exploitation du parc urbain de Houmet-Essouk à Djerba et du cahier des charges y afférent (2009)
Keywords: Urbanisme – Djerba

Ibadites et malékites signent un pacte de paix à Berriane (Winrak, 2009)
Keywords: Conflits – Mzab

Ils ont adressé une lettre au président de la république. Les ibadites demandent l'officialisation de leur rite (El Watan, 2009)
Keywords: Ibadisme – Algérie

Barghash - Loimeier, Roman (Encyclopaedia of Islam, 2009)
Keywords: Biographies – Zanzibar

Historical Memory and Imagined Communities: Modern Ibāḍī Writings on Khārijism - Hoffman, Valerie J. (Historical dimensions of Islam: pre-modern and modern periods ; essays in honor of R. Stephen Humphreys, 2009)
Keywords: Kharijisme

الزعيم الكبير صالح بن يوسف حياته ونضاله - بن الحاج يحيى, الجيلاني (الشركة التونسية للنشر وتنمية فنون الرسم, 2009)
Ibn al-Hajj Yahya Jilani, 2009, Al-Zaʿīm al-Kabīr Ṣālaḥ b. Yūsuf ḥayāta wa naḍāla, Tunis, al-sharika al-tūnisiyya li-funūn al-rasm, 111 p.
Keywords: Ben Youssef; Salah 1907-1961

Themes of the Ibadi/Omani Siyar - Salimi, Abdulrahman al- (Journal of Semitic Studies, 2009)
Keywords: Prosopographie – Oman

PREVOST, V .- L'aventure ibadite dans le Sud tunisien (VIIle-xrne siècle). Effervescence d'une région méconnue. - Custers, Martin H. (Bibliotheca Orientalis, 2009)
Keywords: Recension

CUSTERS, M. H.- Ibadi publishing activities in the East and in the West c. 1880-1960s. An attempt to an inventory, with references to related recent publications - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

CUSTERS, M. H.- Al-Ibadiyya. A bibliography. Volume 1: Ibadis of the Mashriq; Volume 2: Ibadïs of the Maghrib (incl. Egypt); Volume 3: Secondary literature - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

Cohen-Tannoudji Denis (dir.), Entre orient et occident, Juifs et Musulmans en Tunisie, Paris, Éditions de l’éclat, 2007, 379 p. - Abécassis, Frédéric (Revue des mondes musulmans et de la Méditerranée, 2009)
Ce livre est le produit d’une rencontre, tenue à la Sorbonne en avril 2003, entre chercheurs français, tunisiens et israéliens à l’initiative de la Société d’histoire des Juifs de Tunisie. Le colloque s’est tenu sous le quadruple patronage de l’UNESCO, du CNRS, des ministères des Affaires étrangères et de l’Éducation nationale, en impliquant bien d’autres acteurs institutionnels. Sans qu’il n’y soit jamais fait référence, l’ouvrage, paru quatre ans plus tard, porte la marque du contexte dans ...
Keywords: Recension

PREVOST, Virginie, L'aventure ibadite dans le Sud tunisien (VIIIe-XIIIe siècle). Effervescence d'une région méconnue, Tuusula y Helsinki: Academia Scientiarum Fennica, "Humaniora 350", 2008, 479 págs., ilustraciones. - Viguerra Molins, Maria Jesus (Anaquel de Estudios Árabes, 2009)
Keywords: Recension

The Myth of the Sultans in the Western Indian Ocean during the Nineteenth Century: A New Hypothesis - Nicolini, Beatrice (African and Asian Studies, 2009)
Abstract The power of the Al Bu Sa'id Sultans of Oman was widely known as based on delicate balances of forces (and ethnic-social groups), deeply different among them. In fact, the elements that composed the nineteenth century Omani leadership were, and had always been, generally 'divided' amongst three different ethnic groups: the Baluch, the Asian merchant communities and the African regional leaders (Mwiny Mkuu). Within this framework, the role played by European Powers, particularly by the Treaties signed between the Sultans of Oman and the East India Company for abolishing slavery, and by the arms trade was crucial for the development of the Gulf and the Western Indian Ocean international networks They highly contributed to the gradual 'shifting' of the Omanis from the slave trade to clove and spice cultivation – the major economic source of Zanzibar Island – along the coastal area of Sub-Saharan East Africa. The role played by the Omani Sultans – the myth – within the western traditional historiography, which often described them as firmly controlling both the Arabian and African littorals and the major trading ports of the Western Indian Ocean during the nineteenth century, will be reexamined in this paper, taking into account recent research studies and international debates in the topic. The new hypothesis consists of a different perception of the concepts of power and control (political and territorial) of the Western Indian Ocean littorals by the most famous of the Sultans of Oman during the nineteenth century: Saiyid Sa'id bin Sultan Al Bu Sa'id.
Keywords: Zanzibar

Between social skills and marketable skills: the politics of Islamic education in 20th century Zanzibar - Loimeier, Roman (Brill, 2009)
Keywords: Zanzibar

'These Young Men Show No Respect for Local Customs'—Globalisation and Islamic Revival in Zanzibar - Turner, Simon (Journal of Religion in Africa, 2009)
Like elsewhere in Africa, local forms of Islam are being challenged by a number of new reformist and revivalist forms of Islam, influenced to some degree by a global Islamic revival but shaped by particular local histories and politics. This has caused some friction, especially as the regime in place seeks to manipulate these tensions for political benefit. Central to this struggle are the young men who have studied Islam abroad and who challenge the established truths of the traditional religious authorities; these authorities in turn accuse 'the youth' of bringing foreign, 'Arab' ideas and politics to Zanzibar. However, the kind of Islamic revival taking place in Zanzibar is far from radical or violent, and it is not appropriate to pose the present situation in terms of global Salafism versus local Sufism. In fact, Islamic revivalists often coin their critique of the state in terms of human rights and good governance and provide an alternative modernity that simultaneously challenges and articulates secular, liberal forms of modernity. Islamic revival critiques what is perceived as society's moral disorder and the state's inability to deal with new global challenges. Hence the present paper explores how global trends in Islam—but also global discourses on human rights and good governance—influence the current modes of Islamic revival in Zanzibar. With a heavily restricted political field, Islam can be a means of critiquing society without getting involved in politics. However, the government and the traditional religious authorities perceive this revivalism as a threat to the status quo and attempt therefore to politicise the struggle, accusing Islamic movements of fundamentalism and terrorism. It is within this political environment that Islamic revival must navigate.
Keywords: Zanzibar

Social and Intercultural Relations in Nineteenth-Century Zanzibar: Dressed Identity - Vander biesen, Ivan (African and Asian Studies, 2009)
Starting from the nineteenth century descriptive literatures on Zanzibar by authors such as Sir Richard Burton and Charles Guillain, and Salima bint Said-Ruete's autobiography, we can draw a rather detailed picture of the relationship between the different social layers, cultures and genders on Zanzibar. Describing and differentiating the complexity of Zanzibar society in the nineteenth century is the main aim of this paper. The focus is on clothing in order to sketch the social organization of the society and to highlight the cultural relations between the different groups in Zanzibar. The evidence obtained from the description of clothing is used as an eye-opener for the Zanzibar society and this evidence is supported by nineteenth century literature and photography on Zanzibar.
Keywords: Zanzibar

Italian colonial rule and muslim elites in Libya: A relationship of antagonism and collaboration - Baldinetti, Anna (Guardians of Faith in Modern Times: ʿUlamaʾ in the Middle East, 2009)

The Dido Episode in Ercilla's La Araucana and the Critique of Empire - Galperin, Karina; Wright, Elizabeth R. (Hispanic Review, 2009)
Keywords: Littérature – Djerba

Les aléas d'une odyssée - Bouraoui, Hédi (Vermillon, 2009)
Keywords: Littérature – Djerba

Effects of hydro-edaphic environment on the rooting of date palm (Phoenix dactylifera L.) Deglet Noor in the Ouargla Basin (south-east algeria) - Daddi-Bouhoun, Mustapha; Brinis, Louhichi; Saker, Mohamed-Lakhdar; Côte, Marc; Rabier, Jacques (Ecologia mediterranea, 2009)
Keywords: Botanique – Ouargla

Source-Critical Methodologies in Recent Scholarship on the Khārijites - Gaiser, Adam R. (History Compass, 2009)
Keywords: Kharijisme

Le mobilier des synagogues: la Ghriba de Djerba et la Ghriba du Kef - Toumi, Souad (Faculté des Lettres de Manouba, 2009)
Keywords: Judaïsme – Djerba

Insediamenti rupestri nel Gebel Nafusa occidentale (Libia) - Dell'Aquila, Franco; Bencini, Claudio; Fiorentino, Giuseppe (Opera Ipogea, 2009)
Si presenta un quadro degli aspetti ambientali del Gebel Nafusa libico ove sono presenti numerosi episodi di cavità artificiali scavate sia singolarmente sia in agglomerati come villaggi e città. Importanti sono i villaggi rupestri abbandonati perché
Keywords: Architecture – Djebel Nefousa

Libya: Berber Town Beseiged (Africa Research Bulletin: Political, Social and Cultural Series, 2009)
Activists claim that the authorities on December 25th launched a security campaign against the Berber town of Yafran,170km south-west of Tripoli, the Saudi-owned pan-Arab daily Al-Sharq al-Awsat reported. Fathi Bin-Khalifah, coordinatorof the Libyan Action Group and the Lib-yan Amazighs’ Grouping, said in a tele-phone contact from his base in Moroccothat the Libyan authorities were besiegingthe town, electronically jamming telephonecontacts between it and the outside world,and also banning anyone coming fromother areas from entering. He claimed thatthere was intensive security deploymentafter units from the anti-riot Central Sup-port Forces were brought in and that hehad received information that military air-craft had flown over the town which has apopulation of around 50,000.According to assertions by Bin-Khalifahand various Amazigh (Berber) internetwebsites, groups from the ‘‘Youth Lea-gues’’ ofSayf-al-Islam, the second son ofLibyan Leader ColonelMouammar Gad-dafy, and elements from the Revolution-ary Committees attacked the capital ofJabal Nafusah and encircled and raidedthe houses of some known Amazigh fig-ures. Local residents said they did notknow the specific reason for the securitycampaign, while some sources said theLibyan authorities were punishing all theAmazighs because some of their leadershad taken part in an expanded recentconference held to discuss their condi-tions in the Maghreb.But Bin-Khalifah said ‘‘there is no direct orimmediate cause for these events’’ andnoted that the ‘‘International AmazighCongress’’, which adopts the Amazighs’causes from its base in France, had a meet-ing recently with Colonel Gaddafy andadded: ‘‘There are no signs or indications.What happened was sudden and there wereabsolutely no moves beforehand other thanthe regime’s attempt to get rid of thenatives and create a new pit of tension.’’Amazigh activists claim that their influenceand presence in Libyan social, profes-sional, economic, scientific, administrative,and military circles could have aroused thefears of the authorities towards thembecause of their opposition to any attemptto bequeath leadership of the nation toCol. Gaddafy’s son.Yafran with its Amazigh majority is thesecond Libyan town to witness suddentroubles following the violence thatoccurred a few weeks earlier in Al-Kufrahtown in the south of Libya between theLibyan authorities and the local citizens.They were demonstrating against their dete-riorating living conditions and the central authorities’ neglect of their rights to have official identity cards in addition to depriving their sons of the right to government education and other basic services.(Al-Sharq al-Awsat website 27⁄12: BBC Mon.)
Keywords: Vie politique – Djebel Nefousa

Djerba, l’île enchantée de mon enfance - Kindynis, Laris (M-C éditions, 2009)
Recension : - Châabane Harbaoui, al-Jazira, n° 273, Janv. 2012, p. 14. - Merimi, Mohamed, 2010, Rawafid, n. 15, p. 106-112.
Keywords: Littérature – Djerba

Zuaran Berber (Libya): grammar and texts - Mitchell, Terence Frederic; Stroomer, Harry; Oomen, Stanly (Köppe, 2009)
Keywords: Linguistique – Zouara

Weit Gehen - Förster, Eva (Hans Schiller, 2009)

L’extraordinaire histoire de Fatima Mansour - Dryansky, Joanne; Dryansky, Gerry (Héloïse d'Ormesson, 2009)
Keywords: Littérature – Djerba

Confidences sur mon retour en Tunisie - Brébant-Cognard, Andrée (Arabesques éditions, 2009)
Keywords: Littérature – Djerba

The Mosques of Djerba - Hallet, Stanley Ira; Djerbi, Ali (Blurb, 2009)
Keywords: Architecture – Djerba; Monuments – Djerba; Tâjdît; Mosquée (Fâtû; Djerba)

Etude du dimensionnement et de l’état de préservation des chaussées aéronautiques : méthodes ACN / PCN Cas des aéroports de Monastir, Djerba et Tozeur - Neili, Rim (Faculté Des Sciences de Tunis, 2009)
Keywords: Architecture – Djerba

La classification du parler de Jerba (Tunisie) - Brugnatelli, Vermondo (Etudes de phonétique et linguistique berbères: hommage à Naïma Louali, 1961-2005, 2009)
Keywords: Linguistique

كتاب السير - الشماخي, أحمد بن سعيد (دار المدار الإسلامي, 2009)
Ḥasan, Muḥ.: (ed.) (2009) K. al-Siyar, Abū ‘-ʿAbbās Aḥm. b. Abī ʿUthmān Saʿīd b. ʿAbd al-Wāḥid al-Shammākhī. Dirāsa wa-Taḥqīq. 3 vols. Beirut: Dār al-Madār al-Islāmī: 2009, (1112 pp., 24x17 cm.). ISBN 978.9959.29.418.0.*
Keywords: Abu Muhammad Kammus; mosquée (Hachene; Djerba); Bin Ma'zuz; mosquée (Mezraya; Djerba); Jaddi Isa; mosquée (Robbana; Djerba); Monuments – Djerba; Prosopographie – Afrique du Nord; Sidi Salih; mosquée (Bani Bandou; Djerba); Sidī Yaʿīsh; mosquée (Jaabira; Djerba)

سيرة مشايخ نفوسة - البغطوري, مقرين بن محمد (مؤسسة تاولات الثقافية, 2009)
Keywords: Prosopographie – Djebel Nefousa

Djerba et « los Gelves » - Buiza, Gonzola (El Legado andalusi : una nueva sociedad mediterranea, 2009)

Tenue vestimentaire traditionnelle féminine: léthargie ou liberté ? - Mrabet-Robana, Zakia (2009)
Keywords: Moeurs et coutumes – Djerba

Communication on the language, manners and customs of the Berbers or Brebers of Africa: in a series of letters from William Shaler, Esq., Consul of the United States at Algiers to Peter S. Duponceau, Esq. - Shaler, William (Thala éditions, 2009)

Détermination des argiles de potiers par méthode électrique : les argiles de Guellala - Tlet au sud de l’île de Djerba - Khalifa, Fahem; Ben Dahman, Abderrazak; Jouirou, Mohamed (2009)
Keywords: Géologie – Djerba

Modélisation hydrodynamique de la nappe phréatique de Djerba - Ammar, Amel (2009)

Modélisation hydraulique et gestion de renouvellement des conduites du réseau de distribution d’eau potable de l’Ile de Djerba - Ben Younes, Mamdouh (Institut National Agronomique de Tunisie, 2009)

Contribution à la compréhension du fonctionnement du golfe de Gabès : Étude des caractéristiques dynamiques et structurales des communautés phyto-zooplantoniques en relation avec la variabilité environnementale et les caractéristiques hydrographiques des zones côtières et océaniques - Drira, Zaher (Université de Franche-Comté, 2009)

Coastal vulnerability assessment in Djerba (Tunisia) - Duvat, V.; Magnan, Alexandre (Proceedings of the Ninth International Conference on the Mediterranean Coastal Environment, MedCoast 2009, 2009)

Lagoonal sand smelts (atherina lagunaea, teleostei, atherinidae) inhabit marine shallow waters of the coasts of Djerba island (Tunisia) - Bouriga, Nawzet; Selmi, S.; Aurelle, D.; Barthelemy, R.; Quignard, Jean-Pierre; Trabelsi, M.; Faure, E. (Bulletin de l’Institut National des Sciences et Technologies de la Mer, 2009)
Keywords: Littoraux – Djerba

Etude de la dynamique sédimentaire dans la frange littorale de Jerba Ras Taguermess - Ras Marmour - Atoui, Abdelfattah (Ecole Nationale d'Ingénieurs de Tunis, 2009)
Keywords: Littoraux – Djerba

Les analyses statistiques multivariées : application sur deux espèces de Soleidea des cotes Tunisiennes - Glid, A. (Bulletin de l’Institut National des Sciences et Technologies de la Mer, 2009)
Keywords: Botanique – Djerba

Influence of socioeconomic lifestyle factors and genetic polymorphism on type 2 diabetes occurrences among Tunisian Arab and Berber groups of Djerba Island - Baroudi Ouederni, Thouraya; Fadiel, Ahmed; Stambouli, Nejla; Scalize, Trudy J; Ben Maiz, Hedi; Abid, Hafaona Kammoun; Bouhaha, Rym; Sanchez-Corona, Jose; Hamza, Adel; Benammar Elgaaied, Amel (Pharmacogenomics and Personalized Medicine, 2009)
Keywords: Génétique – Djerba

Les mosquées ibadites du Maghreb - Prevost, Virginie (Revue des mondes musulmans et de la Méditerranée, 2009)
Keywords: Architecture – Djerba; Bûlaymân; Mosquée (Ja’bîra; Djerba); Jami al-Kabir; mosquée al- (Hachene; Djerba); Majlis; Mosquée al- (Guellala; Djerba); Monuments – Djerba; Talâkin; Mosquée (Ghizen; Djerba); Tâjdît; Mosquée (Fâtû; Djerba)

Genetic diversity in local barley accessions collected from different geographical regions of Tunisia - Ould Med Mahmoud, M. A.; Hamza, S. (Plant Genetic Resources, 2009)
Keywords: Botanique – Djerba

La ceramica tra l’età punica e la tarda antichità. Le anfore - Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie – Djerba

Peopling the Countryside: Roman Demography in the Albegna Valley and Jerba - Fentress, Elizabeth (Quantifying the Roman Economy: Methods and Problems, 2009)
The surveys of the Albegna Valley and the Island of Jerba were carried out respectively between 1979–1983 and 1995–2000 using similar methodologies (flow data and transect sampling). Each recovered over 1,000 sites, many of them Roman. They thus provide excellent comparable data for the study of ancient demographics. Using standard parameters, approximate densities per kilometre are calculated for each area, allowing the examination of change over time. The low figures for the Albegna Valley are then considered in the light of calculations regarding the population of Italy as a whole.
Keywords: Archéologie – Djerba

Quantifying the Roman Economy - Bowman, Alan; Wilson, Andrew (Oxford University Press, 2009)
Keywords: Djerba – Province romaine d'Afrique

Le produzioni ceramiche dell’isola di Gerba dall’età tardoantica alla prima età islamica: cambiamenti di modelli culturali e tecnologie - Cirelli, Enrico; Fontana, Sergio (Actas del VIII Congreso Internacional de Cerámica Medieval en el Mediterráneo: Ciudad Real-Almagro, del 27 de febrero al 3 de marzo de 2006, 2009)
Keywords: Archéologie – Djerba

Towns and ports - Fentress, Elizabeth (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie – Djerba

The towns and ports - Fentress, Elizabeth; Drine, Ali; Morton, Thomas; Ghalia, T. (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie – Djerba

The rural landscape and economy - Fentress, Elizabeth; Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie – Djerba

The forts - Fentress, Elizabeth (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie – Djerba

Recherches sur le mausolée hellénistique d’Hinshīr Būrgū - Ferchiou, Naïdé (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie – Djerba

The Punic and Libyan Towns of Jerba - Fentress, Elizabeth (Phönizisches und punisches Städtewesen: Akten der internationalen Tagung in Rom vom 21. bis 23. Februar 2007, 2009)
Keywords: Archéologie – Djerba

Tracing Urbanization in Early Modern Jerba - Kahlaoui, Tarek (The Mediterranean medina, 2009)
Keywords: Archéologie – Djerba; Ghuraba; mosquée al- (Houmt Souk; Djerba); Jami al-Kabir; mosquée al- (Hachene; Djerba); Monuments – Djerba

Water supply in the Roman period: aqueducts and cisterns - Wilson, Andrew (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie – Djerba

La ceramica a Jerba tra l’Età Punica e la Tarda Antichità - Capelli, C.; Ben Tahar, Sami; Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie – Djerba

The punic and libyan cemeteries - Ben Tahar, Sami (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie – Djerba

Nouvelle découverte dans la nécropole punique de Soûq el Guébli à Jerba - Ben Tahar, Sami (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2009)
Keywords: Antiquité; Archéologie – Djerba

Lettres d’un imposteur : La construction épistolaire d’une identité : Giorgio Del Giglio Pannilini (v. 1507-v. 1580) - Buttay, Florence (La politique par correspondance : Les usages politiques de la lettre en Italie (xive-xviiie siècle), 2009)
Keywords: Invasions chrétiennes – Djerba

The excavations at Meninx-Tala - Aït Kaci, Ahmed (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie – Djerba

The sacred landscape - Aït Kaci, Ahmed (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie – Djerba

التجارة والتجار في تونس، 1881-1956 - فروة, محمود (كلية العلوم الانسانية والاجتماعية, 2009)
Keywords: Emigration – Djerba – Tunis